Lithium ion secondary battery monomer, preparation method thereof, battery device and power utilization device

By using graphite-based materials and specific alkyne additives in the negative electrode sheet of lithium-ion secondary batteries, combined with the negative electrode thin coating process, the problem of degradation of battery performance and affected room temperature performance at high temperatures is solved, and the battery's good performance and long cycle life at high temperatures and room temperatures are achieved.

CN119890414AActive Publication Date: 2025-04-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510377639.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The performance of lithium-ion secondary batteries in high temperature environments decreases, and the room temperature performance is affected by the increase in the interface impedance of the negative electrode caused by acetic additives.

Method used

By using graphite-based material as the negative electrode active material in the negative electrode sheet and adding specific alkyne additives to the electrolyte, combined with the negative electrode thin coating process, the thickness and porosity of the negative electrode active layer are controlled to optimize the high-temperature and room temperature performance of the battery.

Benefits of technology

It realizes good performance of lithium-ion secondary batteries at high temperatures and room temperatures, reduces the negative electrode interface impedance caused by acetic additives, and extends the battery cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890414A_ABST
    Figure CN119890414A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion secondary battery monomer, a preparation method thereof, a battery device and a power utilization device. The lithium ion secondary battery cell comprises a negative pole piece and an electrolyte, the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, and the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises a graphite-based material, and the mass ratio of the graphite-based material in the negative electrode active material is 60%-100%; the electrolyte comprises one or more of a first alkynyl compound and a second alkynyl compound, and the sum of the mass ratios of the first alkynyl compound and the second alkynyl compound in the alkyne additive is 75%-100%; the negative electrode active layer has a thin thickness (such as less than or equal to 60 [mu] m) on one side of the negative electrode current collector, and the Dv50 of the negative electrode active material is 3-15 [mu] m. The lithium ion secondary battery has good high-temperature performance, and meanwhile, the normal-temperature performance is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion secondary batteries, and further to lithium-ion secondary battery cells and preparation methods thereof, battery devices and power-consuming devices. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] With the development of lithium-ion secondary battery technology, lithium-ion secondary batteries are increasingly widely used in smart phones, tablet computers, laptops, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, and are also widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations. In the storage and use of lithium-ion secondary batteries, not only room temperature environments are involved, but also high temperature scenes are usually inevitably involved. Non-limiting examples include high temperature storage and / or use environments such as summer temperature rise, exposure to the sun, and near the equator. High-temperature additives such as acetylene additives can improve the high temperature performance of the battery by optimizing the negative electrode solid electrolyte interface (SEI) film, but will lead to an increase in the negative electrode interface impedance, affecting the normal temperature performance.

[0004] Therefore, it is necessary to improve both the high temperature performance and the room temperature performance of lithium ion secondary batteries. Summary of the invention

[0005] According to various embodiments and examples of the present application, the present application provides a lithium ion secondary battery cell and a method for preparing the same, a battery device and an electric device. The lithium ion secondary battery has good high temperature performance and significantly improved room temperature performance.

[0006] In some embodiments of the first aspect of the present application, a lithium ion secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is disposed between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%;

[0007] The electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the additive comprises an acetylene additive, and the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; wherein the first acetylene compound is composed of a carbon-carbon triple bond, a C 1-3Alkylene and -OC(=O)-R1, R1 is a Lewis base nitrogen heterocycle; the second alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-O-R2, R2 is C 1-3 Alkyl; the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%;

[0008] The thickness of the negative electrode active layer on one side of the negative electrode current collector is less than or equal to 60 μm, and the D v 50 is 3μm~15μm.

[0009] For a lithium-ion secondary battery whose negative electrode active material mainly includes graphite-based materials and whose electrolyte contains specific acetylene additives (which can be recorded as an "acetylene additive battery system"), the electrolyte includes one or more of a first acetylene compound and a second acetylene compound with a large negative electrode film-forming interface impedance. At this time, the negative electrode active layer of the negative electrode sheet is controlled to have a thin thickness (such as ≤60μm) on one side of the negative electrode current collector by a negative electrode thin coating process, and is matched with a film having a moderate D v 50% of the negative electrode active material can take into account the pressure resistance of the negative electrode active layer in the cold pressing process, the ion transmission path within the overall particles of the negative electrode active material, and the appropriate specific surface area of ​​the negative electrode active material. Relatively small particles are more resistant to cold pressing, and at the same time can control a relatively short ion transmission path. It can also better control the reaction area of ​​the negative electrode active material and thus better control the consumption of the acetylene additive participating in the negative electrode film formation, and better control the increase in the negative electrode interface impedance caused by the introduction of the acetylene additive. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it can better synergistically control the structural stability of the negative electrode active layer, the internal resistance of the battery and the negative electrode interface reaction, and significantly improve the room temperature performance of the acetylene additive battery system.

[0010] In some embodiments, the thickness of the negative electrode active layer on a single side of the negative electrode current collector is 40 μm to 55 μm.

[0011] In some embodiments, the thickness of the negative electrode active layer on a single side of the negative electrode current collector is 45 μm to 55 μm.

[0012] By controlling the thickness of the negative electrode active layer on one side of the negative electrode current collector within the aforementioned range, the combined effects of the negative electrode liquid phase transmission path and the negative electrode interface impedance on the battery internal resistance can be better balanced, and the room temperature performance of the acetylene additive battery system can be more significantly improved.

[0013] In some embodiments, the D of the negative electrode active material v 50 is 3.5μm~15μm.

[0014] By controlling the D v 50 Within the aforementioned range, the use of relatively small negative electrode active materials is conducive to making the negative electrode sheet have a lower tortuosity, which is conducive to better taking into account the pressure resistance of the negative electrode active layer in the cold pressing process, the ion transmission path of the negative electrode active material and the reaction area, and is more conducive to significantly improving the room temperature performance of the acetylene additive battery system.

[0015] In some embodiments, the negative electrode active material includes a coated negative electrode material, wherein the coated negative electrode material includes a negative electrode active body and a carbon coating layer located on at least a portion of the negative electrode active body.

[0016] In some embodiments, the negative electrode active material D v 50 is 5μm~14μm.

[0017] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:

[0018] (a1) The mass proportion of the coated negative electrode material in the negative electrode active material is 80% to 100%;

[0019] (a2) The coated negative electrode material includes coated graphite, and the negative electrode active body in the coated graphite includes a graphite body.

[0020] In some embodiments, the mass proportion of the coated graphite in the negative electrode active material is 80% to 100%.

[0021] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the lithium ion transmission channel on the surface of the negative electrode active material can be optimized, lithium ion transmission can be promoted, and the dynamics of lithium-ion secondary batteries can be improved. At the same time, it is also beneficial to inhibit negative electrode interface side reactions and inhibit the increase in negative electrode interface impedance caused by the participation of acetylene additives in negative electrode film formation, which is beneficial to better improve the room temperature performance of acetylene additive battery systems.

[0022] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, a relatively small negative electrode active material (such as D v 50 is 5μm~14μm) to optimize the rate performance.

[0023] In some embodiments, the porosity of the negative electrode active layer is 14% to 26%.

[0024] In some embodiments, the porosity of the negative electrode active layer is 18% to 22%.

[0025] By controlling the porosity (ε) of the negative electrode active layer within the aforementioned range, the tortuosity of the negative electrode plate can be adjusted, which is beneficial for providing a better lithium ion liquid phase transmission channel, and is also beneficial for achieving better electrolyte infiltration. It can also take into account the electrical contact network between the negative electrode active materials, which is beneficial for comprehensively improving the negative electrode kinetics and cycle performance.

[0026] In some embodiments, the additive further includes an additive B, and the additive B is one or more of a lithium salt additive and a phosphate ester additive, and the mass ratio of the additive B to the acetylene additive is 0.1-100.

[0027] The negative electrode film formation impedance of lithium salt additives and phosphate additives is low. By introducing one or more of lithium salt additives and phosphate additives into the electrolyte, it is beneficial to reduce the impedance of the negative electrode SEI film and reduce the internal resistance of the battery; further, by controlling the mass ratio of additive B to acetylene additives within the aforementioned range, the room temperature performance of the acetylene additive battery system can be better improved.

[0028] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0029] (b1) the mass ratio of the additive B to the acetylene additive is 0.3-50;

[0030] (b2) the lithium salt additive includes one or more of oxalate lithium salt, lithium tetrafluoroborate, lithium difluorophosphate, fluorosulfonic acid lithium salt and lithium perchlorate; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate and lithium bisoxalatoborate; the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethanesulfonate;

[0031] (b3) the phosphate additive includes one or more of silicon-based phosphate additives and alkylphosphonate additives; the silicon-based phosphate additive includes one or more of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)phosphite;

[0032] (b4) the additive includes a lithium salt additive, and the mass proportion of the lithium salt additive in the electrolyte is greater than 0 and less than or equal to 3%;

[0033] (b5) The additive includes a phosphate additive, and the mass proportion of the phosphate additive in the electrolyte is greater than 0 and less than or equal to 1%.

[0034] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:

[0035] (c1) the negative electrode active material comprises a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is less than or equal to 3%;

[0036] (c2) the negative electrode active material comprises a silicon-based material, the silicon-based material comprises a silicon-carbon composite material, the silicon-carbon composite material comprises a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%;

[0037] (c3) The mass proportion of the graphite-based material in the negative electrode active material is 80% to 100%.

[0038] By controlling the content and / or type of silicon-based materials in the negative electrode active material within the aforementioned range, the expansion and contraction changes of the negative electrode can be better controlled, which is conducive to better matching the negative electrode thin coating process with the requirements for the stability of the negative electrode active layer, reducing the generation of fresh interfaces, inhibiting negative electrode interface side reactions, reducing the consumption rate of acetylene additives, and reducing the battery internal resistance growth rate, which is conducive to better improving the battery cycle life. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.

[0039] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide positive electrode material; the thickness of the positive electrode active layer on one side of the positive electrode current collector is less than or equal to 50 μm. In this case, the positive electrode can provide a higher energy density, which can correspond to a thinner positive electrode active layer, and has better capacity matching with the negative electrode active layer, which is conducive to inhibiting negative electrode lithium deposition and extending the battery cycle life, including extending the normal temperature life.

[0040] In some embodiments, the positive electrode active material includes a lithium nickel-based oxide positive electrode material, and the lithium nickel-based oxide positive electrode material includes a lithium element, a non-lithium metal element and an oxygen element; wherein the non-lithium metal element includes a nickel element; in the lithium nickel-based oxide positive electrode material, the ratio of the atomic molar ratio of the nickel element to the sum of the atomic molar ratios of the non-lithium metal elements is recorded as R Ni ; R Ni ≥0.8, the thickness of the positive electrode active layer on one side of the positive electrode current collector is 40 μm to 50 μm. In this case, the capacity matching of the positive electrode active layer and the negative electrode active layer is better, which is more conducive to extending the battery cycle life, including extending the life at room temperature.

[0041] In some embodiments, the mass percentage of the acetylene additive in the electrolyte is 0.001% to 3.2%.

[0042] In some embodiments, the mass percentage of the acetylene additive in the electrolyte is 0.01% to 1.8%.

[0043] By controlling the mass proportion of acetylene additives in the electrolyte within the aforementioned range, the acetylene additives can continue to play a role in repairing the SEI film during the cycle process, which is more conducive to extending the battery cycle life, including extending the life at room temperature.

[0044] In some embodiments, the lithium-ion secondary battery cell satisfies one or more of the following characteristics:

[0045] (d1) The positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium transition metal oxide positive electrode material;

[0046] (d2) The negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is less than or equal to 3%; and the acetylene additive includes the first acetylene compound.

[0047] Alkyne additives can adsorb transition metal ions in the electrolyte.

[0048] When the negative electrode active material includes the aforementioned content of silicon-based material, a fresh interface is generated as the volume of the negative electrode expands and contracts, which leads to interface side reactions and produces acid byproducts. The first alkynyl compound containing a Lewis base nitrogen heterocycle can be used to adsorb the acid byproducts.

[0049] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0050] (e1) the molecular weight of the acetylene additive is less than or equal to 500 Da;

[0051] (e2) The carbon-carbon triple bond in the acetylene additive is CH≡C-;

[0052] (e3) the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 80% to 100%;

[0053] (e4) The mass proportion of the first acetylenic compound in the acetylenic additive is 80% to 100%.

[0054] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0055] (f1) the molecular weight of the acetylene additive is less than or equal to 300 Da;

[0056] (f2) The Lewis base nitrogen heterocycle is a substituted or unsubstituted imidazole group, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 an alkyl group, a cyano group or a fluorine atom;

[0057] (f3) the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 90% to 100%;

[0058] (f4) The mass proportion of the first acetylenic compound in the acetylenic additive is 90% to 100%.

[0059] In some embodiments, the acetylene additive includes one or more of Compound II and Compound III;

[0060] The structure of compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;

[0061] The structure of the compound III is Among them, L 21 C 1-3 Alkylene, R2 is C 1-3 alkyl.

[0062] By controlling the molecular weight of the acetylene additive within the aforementioned lower range, the acetylene additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and better controlling the internal resistance of the battery.

[0063] By controlling the number of carbon-carbon triple bonds in acetylene additives within the aforementioned range, it is beneficial to inhibit the increase in interfacial impedance caused by the participation of acetylene additives in the formation and repair of SEI film, and it is also beneficial to control the influence of acetylene additives on liquid phase impedance; thereby, the increase in battery internal resistance can be better inhibited, and the room temperature performance of acetylene additive battery systems can be better improved.

[0064] The first acetylenic compound includes both a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, which can promote the formation of an organic / inorganic dual-property interface film in the process of participating in the negative electrode interface reaction, thereby improving the stability of the negative electrode SEI film; the Lewis base nitrogen heterocycle can also absorb acid byproducts in the electrolyte, which is beneficial to improving the stability of the negative electrode interface and the negative electrode active material, and is beneficial to reducing the consumption rate of acetylene additives and reducing the growth rate of battery internal resistance; based on the aforementioned multiple effects, but not limited to the aforementioned mechanism, it is beneficial to better improve the room temperature performance of the acetylene additive battery system.

[0065] By controlling the number of Lewis base nitrogen heterocycles in the acetylene additive within the aforementioned range, it is beneficial to better absorb acid byproducts in the electrolyte and also beneficial to control the steric hindrance effect of the Lewis base nitrogen heterocycles on the carbon-carbon triple bond.

[0066] An example of a Lewis base nitrogen heterocycle is the imidazole ring in compound II.

[0067] According to some embodiments of the second aspect of the present application, a method for preparing a lithium-ion secondary battery monomer is provided, which comprises the following steps:

[0068] An electrode assembly including a positive electrode sheet and a negative electrode sheet is placed in a battery housing; wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material, wherein the negative electrode active material includes a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%; wherein the thickness of the negative electrode active layer on a single side of the negative electrode current collector is less than or equal to 55 μm, and the D of the negative electrode active material is less than or equal to 100%. v 50: 3μm~15μm;

[0069] The electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to allow the electrolyte to soak the positive electrode sheet and the negative electrode sheet, and the electrolyte is formed; wherein the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the additive comprises an acetylene additive, and the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; wherein the first acetylene compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-R1, R1 is a Lewis base nitrogen heterocycle; the second alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-O-R2, R2 is C 1-3 Alkyl; the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%.

[0070] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application.

[0071] In some embodiments, the lithium-ion secondary battery monomer described in the first aspect of the present application is prepared.

[0072] According to some embodiments of the third aspect of the present application, a battery device is provided, which includes one or more of the lithium-ion secondary battery monomers described in the first aspect of the present application and the lithium-ion secondary battery monomers prepared by the preparation method of the lithium-ion secondary battery monomer described in the second aspect of the present application;

[0073] In some embodiments, the battery device includes one or more lithium-ion secondary battery cells.

[0074] The number of lithium-ion secondary batteries in the battery device can be controlled according to capacity requirements.

[0075] In some embodiments of the fourth aspect of the present application, an electrical device is provided, which includes at least one of the lithium-ion secondary battery cell described in the first aspect of the present application, the lithium-ion secondary battery cell prepared by the preparation method of the lithium-ion secondary battery cell described in the second aspect of the present application, and the battery device described in the third aspect of the present application.

[0076] The details of one or more implementations or embodiments of the present application are set forth in the following drawings and description. Other features, objects and advantages of the present application will become apparent from the description, drawings and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] In order to better describe and illustrate the embodiments, examples or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments, examples or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0078] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0079] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0080] Figure 3 FIG. 1 is a schematic diagram of a battery device according to an embodiment of the present application.

[0081] Figure 4A schematic diagram of a battery pack according to an embodiment of the present application.

[0082] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0083] Figure 6 It is a schematic diagram of an electrical device using a lithium-ion secondary battery cell according to an embodiment of the present application as a power source.

[0084] Description of reference numerals:

[0085] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery device; 5. Battery cell; 51. Battery casing; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION

[0086] Below, some embodiments and examples of the lithium-ion secondary battery cell and its preparation method, battery device and power device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0087] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0088] In the present application, "numerical value" is involved, and its meaning includes the present number and its reasonable approximation. The definition of "numerical value" can be applied to discrete numerical points and the endpoints of the numerical range. If not specifically limited, "approximation" is involved, covering the numerical interval based on the reasonable fluctuation range of the present number, and the reasonable fluctuation range may vary due to the type and numerical size of the present number. The reasonable fluctuation range can be reasonably confirmed according to the accuracy of the test or measurement method. Therefore, when it comes to numerical values ​​or numerical ranges, if there is no special explanation, it should be understood that the numerical value covers its reasonable approximation, and the numerical range covers the reasonable approximation of the two endpoints. Those skilled in the art can understand that the acceptable fluctuation range of the relevant approximation can be included in the definition of the numerical value or the numerical range. In the present application, if there is no other explanation, "N1" can be reasonably understood as "about N1", and "N1~N2" can be reasonably understood as "about N1 to about N2", wherein N1 and N2 are two unequal numerical values.

[0089] In this application, unless otherwise specified, "about" means within a reasonable range above and below the number, and the fluctuation range may vary depending on the type and value of the number. For example, it may be allowed to be within a range of ±10%, ±5%, ±2%, ±1%, etc. For example, taking "about 20°C" and its approximate value of ±1°C as an example, the approximate values ​​of 19°C, 19.5°C, etc. within the approximate range shown in "about 20°C" should also be included in the range indicated by "about 20°C".

[0090] In this application, when "multiple", "multiple", "multiple" and the like are involved, unless otherwise specified, they refer to a number greater than or equal to 2. For example, "one or more" means one or ≥ (greater than or equal to) two. It is understood that when "any number" of items are involved, it refers to any suitable combination of multiple items, that is, the combination of "any number" of items is performed in a manner that does not conflict and can implement this application.

[0091] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0092] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0093] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, a includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "a consists of a1, a2 and a3" or "a is selected from a1, a2 and a3", and the feature or solution of "a includes not only a1, a2 and a3, but also other members".

[0094] In the present application, unless otherwise specified, M (such as m1) means that m1 is a non-limiting example of M, and it can be understood that M is not limited to m1.

[0095] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel solutions of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. Unless otherwise specified, the descriptions of "optionally include", "optionally include", etc. in this application, taking "optionally include" as an example, mean "may include or not include".

[0096] In the present application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein any and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "M and / or N" means a group consisting of M, N, and "a combination of M and N". Among them, "including M and / or N" can mean "including M, including N, and including M and N", and can also mean "including M, including N, or including M and N", which can be properly understood according to the sentence in which it is located.

[0097] Herein, the word “suitable” in “suitable combination”, “suitable method”, etc., shall be based on the technical solution that can implement the present application.

[0098] Herein, "preferred", "better", "good", etc. are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0099] In the present application, “further”, “furthermore”, “particularly”, “for example”, “such as”, “example”, etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present application.

[0100] In the present application, the terms "first", "second", "third", "fourth", etc. in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0101] In the description of the present application, it should be understood that the terms "thickness", "height", "up", "down", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0102] In this application, unless otherwise clearly specified or limited, the terms "connected" and "connection" related to mechanical structures should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection. For ordinary technicians in this field, the meanings of the above terms in this application can be understood according to the circumstances.

[0103] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean a relative positional relationship in terms of horizontal height, or may mean that there is an attachment relationship without limiting the relative positional relationship in terms of horizontal height.

[0104] In this application, the term "room temperature" or "normal temperature" generally refers to 4°C to 35°C, and may refer to 20°C ± 5°C. In some embodiments or examples of this application, room temperature refers to 20°C to 30°C. In some embodiments or examples of this application, "normal temperature" is 20°C to 35°C, and may be 20°C to 30°C.

[0105] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5 μm or 3-5 μm both mean that the units of the left endpoint "3" and the right endpoint "5" are both μm (micrometers), which have the same meaning as 3 μm ~5 μm. In addition, similar descriptions of other parameters such as temperature and size are also understood in the same way.

[0106] In this application, unless otherwise specified, the term "molecular weight" refers to the molecular weight measured in Daltons (Da), where 1 Dalton is equal to 12 One twelfth of the atomic mass of C.

[0107] In this application, "greater than or equal to", "greater than or equal to" and "≥" have the same meaning and can be used interchangeably; "less than or equal to", "less than or equal to" and "≤" have the same meaning and can be used interchangeably; "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In this application, unless otherwise specified, "greater than or equal to" and "≥" can be regarded as providing two solutions of "greater than" and "equal to". In this application, unless otherwise specified, "less than or equal to" and "≤" can be regarded as providing two solutions of "less than" and "equal to".

[0108] In the present application, exemplary descriptions such as "in some implementation modes (or examples)" and "in one implementation mode (or example)" may include but are not limited to the following meanings: these solutions may be combined with other solutions in a suitable manner to form new technical solutions.

[0109] The improved effects described in this application, unless otherwise stated, are not intended to be limited to any theory.

[0110] During the storage and use of lithium-ion secondary batteries, not only room temperature environments are involved, but also high temperature scenes are usually inevitably involved. Non-limiting examples include high temperature storage and / or use environments such as summer temperature rise, exposure to the sun, and near the equator. High-temperature additives such as acetylene additives can improve the high-temperature performance of the battery by optimizing the negative electrode solid electrolyte interface (SEI) film, but will increase the negative electrode interface impedance and affect the normal temperature performance. It is necessary to improve both the high temperature performance and the normal temperature performance of lithium-ion secondary batteries.

[0111] According to various embodiments and examples of the present application, the present application provides a lithium ion secondary battery cell and a method for preparing the same, a battery device and an electric device. The lithium ion secondary battery has improved high temperature performance and room temperature performance at the same time.

[0112] In some embodiments, a lithium-ion secondary battery cell comprises a negative electrode plate and an electrolyte; the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, the negative electrode active layer comprises a negative electrode active material, and the negative electrode active material comprises a graphite-based material; the electrolyte comprises one or more of a first alkynyl compound and a second alkynyl compound; the negative electrode active layer has a relatively thin thickness (e.g., less than or equal to 60 μm) on one side of the negative electrode current collector, and the negative electrode active material has a D v 50 is 3μm~15μm. The lithium ion secondary battery has good high temperature performance and significantly improved room temperature performance.

[0113] In some embodiments, the lithium-ion secondary battery cell comprises a negative electrode plate and an electrolyte; the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, the negative electrode active layer comprises a negative electrode active material; the electrolyte comprises one or more of a first alkynyl compound and a second alkynyl compound; the thickness Ds of the negative electrode active layer on one side of the negative electrode current collector is greater than the thickness Ds of the negative electrode active material. v 50 (denoted as D v 50 N ) ratio (R x =Ds / D v 50 N ) may be less than 20. Further optionally, the D v 50 is 3 μm to 15 μm. In some embodiments, the negative electrode active material includes a graphite-based material. The lithium ion secondary battery has good high temperature performance and significantly improved room temperature performance.

[0114] In some embodiments, a lithium-ion secondary battery cell comprises a negative electrode plate and an electrolyte; the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises a graphite-based material; the electrolyte comprises an acetylene additive, the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; the negative electrode active layer has a relatively thin thickness (e.g., less than or equal to 60 μm) on one side of the negative electrode current collector, and the negative electrode active material has a D v 50 is 3 μm to 15 μm. The lithium-ion secondary battery has good high temperature performance and significantly improved room temperature performance. In some embodiments, the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%.

[0115] In some embodiments, the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%, and can be optionally 80% to 100%.

[0116] In some embodiments, the first alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 It is composed of an alkylene group and -OC(=O)-R1, and R1 is a Lewis base nitrogen heterocycle.

[0117] In some embodiments, the second alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-O-R2, R2 is an alkyl group, which can be C 1-3 alkyl.

[0118] In some embodiments, a lithium-ion secondary battery cell comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is disposed between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the additive comprises an acetylene additive, wherein the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; the negative electrode active layer has a relatively thin thickness (e.g., less than or equal to 60 μm) on a single side of the negative electrode current collector, and the D of the negative electrode active material is less than or equal to 100%. v 50 is 3 μm~15 μm. The lithium ion secondary battery has good high temperature performance and significantly improves room temperature performance. In some embodiments, the sum of the mass proportions of the first acetylenic compound and the second acetylenic compound in the acetylenic additive is 75%~100%, and can be optionally 80%~100%.

[0119] In this application, unless otherwise specified, the "high temperature" during battery cycling and / or storage may be greater than 35°C and less than or equal to 80°C, optionally, greater than 35°C and less than or equal to 60°C, further optionally 37°C to 60°C, further optionally 40°C to 60°C, and further optionally 45°C to 60°C, but not limited thereto. The "high temperature" during battery storage or cycling may also be any of the following temperatures or a range consisting of any two of the following temperatures: 36°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0120] In this application, unless otherwise specified, the "normal temperature" during battery circulation and / or storage may be 20°C to 35°C, optionally 20°C to 30°C, but not limited thereto. The "high temperature" during battery storage or circulation may also be any of the following temperatures or a range consisting of any two of the following temperatures: 20°C, 22°C, 24°C, 25°C, 26°C, 28°C, 30°C, 32°C, 34°C, 35°C, etc.

[0121] In this application, unless otherwise specified, the term "lithium-ion secondary battery" refers to a secondary battery whose active ions include lithium ions, and a "lithium-ion secondary battery cell" is a battery cell whose active ions include lithium ions. Typically, a lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. A separator is provided between the positive electrode sheet and the negative electrode sheet. The separator mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0122] In the present application, unless otherwise specified, the "electrode active material layer" includes at least one of the positive electrode active material layer of the positive electrode sheet and the negative electrode active material layer of the negative electrode sheet. Depending on the detailed circumstances, the electrode active material layer may refer to the positive electrode active material layer or the negative electrode active material layer. It can be understood that the positive electrode active material layer contains positive electrode active materials, and the negative electrode active material layer contains negative electrode active materials. In the present application, the "electrode active material layer" may also be recorded as the "active material layer", the "positive electrode active material layer" may also be recorded as the "positive electrode active layer", and the "negative electrode active material layer" may also be recorded as the "negative electrode active layer".

[0123] In this application, the terms "electrode plate" and "electrode plate" have the same meaning and can be used interchangeably. The electrode plate can be a positive electrode plate or a negative electrode plate, and the "active material" or "active substance" in the electrode plate has the ability to reversibly embed and extract active ions.

[0124] In the present application, the term "negative electrode sheet" includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material. The term "negative electrode active material" refers to a material used in a negative electrode sheet that can reversibly insert and extract active ions.

[0125] In this application, unless otherwise specified, "negative electrode sheet" includes a negative electrode current collector. "Negative electrode current collector" refers to a structure responsible for collecting and conducting electrons at the negative electrode. In the negative electrode sheet, the negative electrode active layer is located on at least one side of the negative electrode current collector, and can be located on one side or both sides of the negative electrode current collector.

[0126] In the present application, the term "positive electrode sheet" includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material. The term "positive electrode active material" refers to a material used in a positive electrode sheet that can reversibly extract and insert active ions.

[0127] In this application, unless otherwise specified, "positive electrode sheet" includes positive electrode current collector. "Positive electrode current collector" refers to the structure responsible for collecting and conducting electrons at the positive electrode. In the positive electrode sheet, the positive electrode active layer is located on at least one side of the positive electrode current collector, and can be located on one side or both sides of the positive electrode current collector.

[0128] In the present application, unless otherwise specified, "separation membrane" and "diaphragm" have the same meaning and can be used interchangeably.

[0129] In a first aspect of the present application, a lithium ion secondary battery is provided, which has good high temperature performance and significantly improved room temperature performance.

[0130] In some embodiments, a lithium ion secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is disposed between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes a graphite-based material; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the additive includes an acetylene additive, wherein the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive includes one or more of a first acetylene compound and a second acetylene compound; the negative electrode active layer has a relatively thin thickness (e.g., less than or equal to 60 μm) on one side of the negative electrode current collector, and the D of the negative electrode active material is less than or equal to 1 μm. v 50 is 3 μm to 15 μm. In some embodiments, the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%.

[0131] In some embodiments, the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%, and can be optionally 80% to 100%.

[0132] In some embodiments, a lithium ion secondary battery is provided, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein a separator is disposed between the positive electrode plate and the negative electrode plate; the negative electrode plate includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the additive includes an acetylene additive, wherein the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive includes one or more of a first acetylene compound and a second acetylene compound; the sum of the mass proportions of the first acetylene compound and the second acetylene compound in the acetylene additive is 75% to 100%, and may be 80% to 100%; the thickness of the negative electrode active layer on a single side of the negative electrode current collector is less than or equal to 60 μm, and the D of the negative electrode active material is less than or equal to 100%. v 50 is 3μm~15μm.

[0133] In the present application, unless otherwise specified, "graphite-based material" refers to a negative electrode active material containing a graphite matrix. Unless otherwise specified, "graphite matrix" refers to a matrix composed of graphite. Unless otherwise specified, the mass proportion of the graphite matrix in the graphite-based material can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%. Without limitation, the graphite-based material may include one or more of a coated graphite-based material and uncoated graphite. The coated graphite-based material includes a graphite matrix and a coating layer located on at least a portion of the surface of the graphite matrix. It can be understood that the coating layer is different from the material in the graphite matrix.

[0134] In some embodiments, the mass proportion of graphite-based materials in the negative electrode active material is 60%~100%, optionally 70%~100%, further optionally 75%~100%, further optionally 80%~100%, further optionally 90%~100%, further optionally 95%~100%, further optionally 97%~100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0135] In the present application, unless otherwise specified, the "thickness of the negative electrode active layer on one side of the negative electrode current collector" in a lithium-ion secondary battery may be simply referred to as the "thickness of the negative electrode active layer on one side"; the "total thickness of the negative electrode active layer on both sides of the negative electrode current collector" in a lithium-ion secondary battery may be simply referred to as the "total thickness of the negative electrode active layer".

[0136] In the present application, unless otherwise specified, "non-aqueous solvent" refers to a solvent that is not water.

[0137] In the present application, unless otherwise specified, a "carbon-carbon triple bond" refers to an unsaturated bond having a -C≡C- skeleton.

[0138] In this application, unless otherwise specified, "acetylene additives" refer to additives containing carbon-carbon triple bonds. Acetylene additives can participate in the formation of the negative electrode solid electrolyte interface (SEI) film. Acetylene additives can significantly improve the high temperature performance of the battery, including extending the high temperature cycle and storage life, and can be used as high temperature additives. However, the introduction of some acetylene additives such as one or more of the first acetylene compound and the second acetylene compound can easily lead to a large negative electrode interface impedance at room temperature, thereby affecting the room temperature performance of the battery.

[0139] In this application, unless otherwise specified, the "first alkynyl compound" refers to an acetylene additive containing a carbon-carbon triple bond and a Lewis base nitrogen heterocycle. The carbon-carbon triple bond and the Lewis base nitrogen heterocycle in the first alkynyl compound are connected by a linker L1, and the linker L1 generally contains a C covalently bonded to the carbon-carbon triple bond. 1-3 For example, the first alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 It is composed of an alkylene group and -OC(=O)-R1, and R1 is a Lewis base nitrogen heterocycle.

[0140] In this application, unless otherwise specified, "Lewis base nitrogen heterocycle" refers to a nitrogen heterocycle with Lewis base properties. This concept is based on Lewis acids and bases theory. Lewis base nitrogen heterocycles can donate electron pairs and have electron-rich properties. Therefore, Lewis base nitrogen heterocycles can attract and bind acidic substances. Non-limiting examples of Lewis base nitrogen heterocycles include imidazole rings, but are not limited thereto.

[0141] In the present application, unless otherwise specified, "nitrogen heterocyclic structure" refers to a cyclic structure in which the ring-forming atoms include nitrogen atoms. The term "ring-forming atoms" refers to the constituent atoms of the ring skeleton. As a non-limiting example, the three carbon atoms and two nitrogen atoms in the imidazole ring are ring-forming atoms, and the imidazole ring is a 5-membered ring. "Ring-forming nitrogen atoms" refers to nitrogen atoms in the ring-forming atoms.

[0142] In the present application, unless otherwise specified, the "second alkynyl compound" is an acetylenic additive containing a carbon-carbon triple bond and an alkyl carbonate group, wherein the structure of the alkyl carbonate group is R2-OC(=O)-O-*, wherein * is a bonding site connected to the carbon atom, R2 is an alkyl group, and can further be C 1-3 The carbon-carbon triple bond in the second alkynyl compound and the alkyl carbonate group are connected by a linker L2, which usually contains a C covalently bonded to the carbon-carbon triple bond. 1-3 For example, the second alkynyl compound can be composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-O-R2, R2 is an alkyl group, and can be further C 1-3 alkyl.

[0143] In the lithium-ion secondary battery provided in the present application, it can be understood that the positive electrode plate and the negative electrode plate are soaked in the electrolyte.

[0144] The negative electrode plate of the lithium-ion secondary battery adopts a thin coating process, and the thickness of the negative electrode active layer is relatively thin, such as less than or equal to 60 μm, which can improve the diffusion distance of lithium ions in the negative electrode plate, and to a certain extent help to compensate for the increase in interface impedance caused by the introduction of acetylene additives; however, the cold pressing process of the thin coating process may face problems such as coating cracking, and the negative electrode plate is required to have a certain mechanical strength. Small particles have better pressure resistance, but the small particles have a large specific surface area, which will aggravate the negative electrode interface side reactions and thus easily aggravate the increase in negative electrode interface impedance caused by acetylene additives.

[0145] For a lithium-ion secondary battery whose negative electrode active material mainly includes graphite-based materials and whose electrolyte contains specific acetylene additives (which can be recorded as an "acetylene additive battery system"), the electrolyte includes one or more of a first acetylene compound and a second acetylene compound with a large negative electrode film-forming interface impedance. At this time, the negative electrode active layer of the negative electrode sheet is controlled to have a thin thickness (such as ≤60μm) on one side of the negative electrode current collector by a negative electrode thin coating process, and is matched with a film having a moderate D v 50% of the negative electrode active material can take into account the pressure resistance of the negative electrode active layer in the cold pressing process, the ion transmission path within the overall particles of the negative electrode active material, and the appropriate specific surface area of ​​the negative electrode active material. Relatively small particles are more resistant to cold pressing, and at the same time can control a relatively short ion transmission path. It can also better control the reaction area of ​​the negative electrode active material and thus better control the consumption of the acetylene additive participating in the negative electrode film formation, and better control the increase in the negative electrode interface impedance caused by the introduction of the acetylene additive. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it can better synergistically control the structural stability of the negative electrode active layer, the internal resistance of the battery and the negative electrode interface reaction, and significantly improve the room temperature performance of the acetylene additive battery system.

[0146] The single-side thickness or total thickness of the negative electrode active layer in the lithium-ion secondary battery can be obtained by testing using methods known in the art. For example, the surface of the substrate with and without the negative electrode active layer to be tested can be compared, for example, the test can be performed by a step meter test method. The stylus of the step meter gently rubs across the sample surface with a very small force, and the micron or even nanometer-level ups and downs of the sample surface are amplified millions of times by the sensor connected to the stylus, and then converted into an electronic signal, input into the software, and finally displayed in the form of digital and graphical data.

[0147] The thickness of the negative electrode active layer to be measured can also be obtained by statistically analyzing the results of multiple positions of a scanning electron microscope (SEM) photograph of a section in the thickness direction of the electrode piece.

[0148] You can also use a micrometer to measure. You can test it by the following method: disassemble the battery cell, take out the negative electrode, and use a micrometer to measure the thickness of the electrode D ATake another negative electrode sheet, wipe off the negative electrode active layer on the surface of the side to be tested, and remove the remaining empty current collector foil. Test the thickness D 10 , then the thickness of the negative electrode active layer on the negative electrode current collector is D A -D 10 Take another negative electrode sheet, wipe off the negative electrode active layer on both sides of the surface to leave the remaining empty current collector foil, and test the thickness D0. The total thickness of the negative electrode active layer on both sides of the negative electrode current collector in the lithium-ion secondary battery is D A -D0.

[0149] The types and concentrations of inorganic components in the electrolyte (including electrolyte salts and inorganic additives) can be tested with reference to relevant standards such as GB / T 34672-2017 General Rules for Ion Chromatography of Chemical Reagents, JY / T020-1996 General Rules for Ion Chromatography Analysis Methods, and GB / T 6040-2019 General Rules for Infrared Spectroscopy Analysis Methods, and updated versions of standard methods can be preferred. The types and content tests of organic components in the electrolyte (including non-aqueous solvents and organic additives) can be tested with reference to relevant standards such as GB / T 9722-2023 General Rules for Gas Chromatography of Chemical Reagents.

[0150] In addition, those skilled in the art can also identify the components contained in the electrolyte of the lithium-ion secondary battery by one or more of the following detection methods, including but not limited to: nuclear magnetic resonance hydrogen spectroscopy ( 1 H NMR) method, high performance liquid chromatography (HPLC) method, matrix-assisted laser desorption-mass spectrometry (MADI-TOF) method, Fourier transform infrared spectroscopy (FT-IR) method, ultraviolet spectroscopy, gas chromatography (GC) method, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics. As a non-limiting example, FT-IR, ultraviolet spectroscopy, 1 The component types and contents of the electrolyte are detected by one or more methods such as H NMR, mass spectrometry, MADI-TOF, GC, etc., but are not limited thereto.

[0151] The sample of electrolyte to be tested can be obtained by disassembling the battery cell.

[0152] In some embodiments, in a lithium-ion secondary battery, the thickness of the negative electrode active layer on either side of the negative electrode current collector is 40 μm to 60 μm, which can be 40 μm to 55 μm, and further 45 μm to 55 μm, and can also be any of the following thicknesses or a range consisting of any two of the following thicknesses: 40 μm, 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 55 μm, 56 μm, 58 μm, 60 μm. In some embodiments, in a lithium-ion secondary battery, the thickness of the negative electrode active layer on either side of the negative electrode current collector is less than or equal to any of the following thicknesses: 50 μm, 52 μm, 54 μm, 55 μm, 56 μm, 58 μm, 60 μm, etc. In some embodiments, in the lithium ion secondary battery, the thickness of the negative electrode active layer on either side of the negative electrode current collector is greater than or equal to any of the following thicknesses: 40 μm, 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, etc.

[0153] In some embodiments, in the lithium ion secondary battery, the total thickness of the negative electrode active layer on both sides of the negative electrode current collector is 80μm~120μm, which can be 80μm~110μm, and can be further selected as 90μm~110μm. It can also be any of the following thicknesses or a range consisting of any two of the following thicknesses: 80μm, 82μm, 84μm, 85μm, 86μm, 88μm, 90μm, 92μm, 94μm, 95μm, 96μm, 98μm, 110μm, 112μm, 114μm, 115μm, 116μm, 118μm, 120μm, etc.

[0154] In some embodiments, the surface density of the negative electrode active layer on one side of the negative electrode current collector is (0.05-0.15) g / 1540.25 mm 2 , optional: (0.05~0.12)g / 1540.25mm 2 , further optional as (0.08~0.12)g / 1540.25mm 2 , can also be (0.08~0.15) g / 1540.25mm 2 , optional: (0.085~0.14)g / 1540.25mm 2 , can also be any of the following values ​​or a range consisting of any two of the following values: 0.05g / 1540.25mm 2 , 0.055 g / 1540.25 mm 2 , 0.06 g / 1540.25 mm 2 , 0.065 g / 1540.25 mm 2 , 0.07 g / 1540.25 mm 2, 0.075 g / 1540.25 mm 2 , 0.08g / 1540.25mm 2 , 0.085 g / 1540.25 mm 2 , 0.09g / 1540.25mm 2 , 0.095 g / 1540.25 mm 2 , 0.10 g / 1540.25 mm 2 , 0.11 g / 1540.25 mm 2 , 0.12 g / 1540.25 mm 2 , 0.13 g / 1540.25 mm 2 , 0.135 g / 1540.25 mm 2 , 0.14 g / 1540.25 mm 2 , 0.145 g / 1540.25 mm 2 , 0.148 g / 1540.25 mm 2 , 0.15 g / 1540.25 mm 2 Etc. The mass proportion of graphite-based materials in the negative electrode active material can be further controlled within a more appropriate range.

[0155] Graphite-based material is a carbon-based material. It is understood that the negative electrode active material includes a carbon-based material. The carbon-based material may include one or more of graphite, soft carbon and hard carbon. Graphite may include one or more of artificial graphite and natural graphite. Non-limitingly, the mass proportion of graphite-based material in carbon-based material can be 60%~100%, optionally 80%~100%, further 90%~100%, further 97%~100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc. The surface density of the negative electrode active layer on the single side of the negative electrode current collector can be further controlled to be (0.05~0.15) g / 1540.25mm 2 , or any suitable value or range within this range.

[0156] In some embodiments, the carbon-based material may include one or more of artificial graphite, natural graphite, soft carbon, and hard carbon.

[0157] In some embodiments, the carbon-based material is a graphite-based material.

[0158] In some embodiments, the negative electrode active material is a graphite-based material.

[0159] In this application, unless otherwise specified, "area density of the negative electrode active layer on one side of the negative electrode current collector" refers to the ratio of the mass of the negative electrode active layer on one side of the negative electrode current collector to the area of ​​the negative electrode active layer on that side, and the corresponding "area" is equal to the positive projection area of ​​the negative electrode active layer along the thickness direction of the electrode sheet. "Area density of the negative electrode active layer on one side of the negative electrode current collector" can also be recorded as "unilateral density of the negative electrode active layer".

[0160] In a non-limiting manner, the following method can be used to test the surface density of the negative electrode active layer on one side of the negative electrode current collector: disassemble the battery to obtain the negative electrode sheet, erase the negative electrode active layer on one side of the obtained negative electrode sheet, and only retain the negative electrode active layer on the single side, and punch it into an area S0 (e.g., 1540.25mm 2 ) and measure the mass M of the small disc. B , take the negative electrode sheet from another area, wipe off the negative electrode active layer on the surface and remove the remaining negative electrode current collector foil (which can be recorded as empty negative electrode current collector foil), and also punch it into small discs with an area of ​​S0. Weigh the mass of the empty negative electrode current collector foil and record it as M0. Then the surface density of the negative electrode active layer on one side of the negative electrode current collector is ρ S =(M B -M0) / S0.

[0161] In some embodiments, the thickness of the negative electrode active layer on a single side of the negative electrode current collector is less than or equal to 60 μm, and can also be less than or equal to any of the following thicknesses: 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 55 μm, 56 μm, 58 μm, etc.

[0162] In some embodiments, the thickness of the negative electrode active layer on a single side of the negative electrode current collector is 40 μm to 60 μm, which can be 40 μm to 55 μm, and can be further 45 μm to 55 μm. It can also be any of the following thicknesses or a range consisting of any two of the following thicknesses: 40 μm, 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 55 μm, 56 μm, 58 μm, 60 μm, etc.

[0163] By controlling the single-side thickness and / or total thickness of the negative electrode active layer on the negative electrode current collector within the aforementioned range, the combined effects of the negative electrode liquid phase transmission path and the negative electrode interface impedance on the battery internal resistance can be better balanced, and the room temperature performance of the acetylene additive battery system can be more significantly improved.

[0164] In some embodiments, the D of the negative electrode active material v50 is 3μm~15μm, and can be optionally 3.5μm~15μm, and can be further optionally 3.8μm~10μm. It can also be any of the following values ​​or a range consisting of any two of the following values: 3μm, 3.5μm, 3.8μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.

[0165] In the context of this application, the volume cumulative distribution particle size D v N (where N represents any value selected from 0 to 100) is used to characterize the particle size of the material, which refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches N%, and the particle size is less than or equal to D v The volume percentage of N is N%. v N can be obtained from the volume cumulative distribution curve of the material particle size. If there is no other explanation, the volume cumulative distribution curve starts from zero from the small particle size side. v 50 is used as an example. In this application, unless otherwise specified, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. This parameter indicates that the particle size of particles accounting for 50% of the volume of the material is less than or equal to D v 50, and 50% of the particles by volume are larger than D v 50. Those skilled in the art will appreciate that v 50. D v 3. D v 1, etc., and can be measured by instruments and methods known in the art. For example, it can be conveniently measured by laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as Mastersizer 2000E laser particle size analyzer and LS-909 laser particle size analyzer (OMEC) of Malvern Instruments Ltd., UK. Further, for equipment models such as Malvern 2000 (MasterSizer 2000) laser particle size analyzer, the standard process GB / T19077-2016 / ISO 13320:2009 can be referred to for testing.

[0166] By controlling the D v 50 Within the aforementioned range, the use of relatively small negative electrode active materials is conducive to making the negative electrode sheet have a lower tortuosity, which is conducive to better taking into account the pressure resistance of the negative electrode active layer in the cold pressing process, the ion transmission path of the negative electrode active material and the reaction area, and is more conducive to significantly improving the room temperature performance of the acetylene additive battery system.

[0167] In some embodiments, the following method can be used to test the D of the negative electrode active material or the positive electrode active material: v 50. D v 3. D v 1, etc. Malvern 2000 (MasterSizer 2000) laser particle size analyzer was used, and the reference standard process was GB / T19077-2016 / ISO 13320:2009. The detailed test process included: taking an appropriate amount of the sample to be tested, adding a solvent (the solvent can be deionized water, and the sample concentration can be controlled at 8%~12% shading), and ultrasonic treatment for 5 min (53KHz / 120W) to fully disperse the sample, and then measuring the sample according to GB / T19077-2016 / ISO 13320:2009 standard. Non-limiting examples of solvents include deionized water and anhydrous ethanol. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light. A particle size volume distribution diagram is drawn based on the test data, and D is obtained from the distribution diagram. v 50 and other parameters. In order to avoid the influence of agglomeration in the drying process on the particle size test, the washed wet sample was taken for dispersion test.

[0168] Unless otherwise specified, the thickness of the negative electrode active layer on one side of the negative electrode current collector can be recorded as Ds, and the D v 50 can be recorded as D v 50 N ; The thickness of the negative electrode active layer on the negative electrode current collector (Ds) and the D v The ratio of 50 is recorded as R x , R x =Ds / D v 50 N In some embodiments, R x It can be less than 20, further can be 5 to 18, further can be 6 to 18, further can be 6.5 to 18, further can be 8 to 18, further can be 10 to 18, and can also be any of the following suitable values ​​or a suitable range consisting of any two of the following values: 3, 3.1, 3.2, 3.4, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, etc.; R x It can also be any of the following ranges: 5~16, 6~16, 6.5~16, 8~16, 10~16, 5~16, etc.

[0169] In some embodiments, the D of the negative electrode active material v 1 is greater than or equal to 1 μm.

[0170] In some embodiments, the D of the negative electrode active material v 1 is greater than or equal to 1.5 μm.

[0171] By controlling the D v 1 Within the aforementioned range, the negative electrode interface side reactions can be significantly inhibited, the consumption rate of acetylene additives can be reduced, and the battery internal resistance growth rate can be reduced.

[0172] The tortuosity of the negative electrode active layer is denoted as τ.

[0173] In some embodiments, 4≤τ≤6, optionally, 4≤τ≤5.4, further optionally, 4≤τ≤5.1. Without limitation, the tortuosity (τ) of the negative electrode active layer can also be any of the following values ​​or a range selected from any two of the following values: 4, 4.1, 4.2, 4.4, 4.5, 4.6, 4.8, 5.0, 5.1, 5.2, 5.4, 5.5, 5.6, 5.8, 6, etc.

[0174] In the present application, the "tortuosity" of the negative electrode active layer can also be described as the tortuosity or tortuosity of the negative electrode sheet. The tortuosity of the negative electrode active layer reflects the degree of tortuosity of the path of the pore communication passage through which the active ions pass when passing through a certain thickness of the negative electrode active layer. Numerically, the tortuosity τ of the negative electrode active layer can be equal to the ratio of the actual path length of the pore communication passage between the two side surfaces of the negative electrode active material layer to the thickness of the negative electrode active material layer. The theoretical minimum value of the tortuosity is 1. At this time, the pore communication passage is a straight through hole, and the corresponding actual path is the shortest, which is numerically consistent with the thickness of the negative electrode active layer. The greater the tortuosity, the higher the degree of tortuosity of the path of the pore communication passage. Conversely, the smaller the tortuosity, the lower the degree of tortuosity of the path of the pore communication passage. The value of the tortuosity is related to factors such as the particle size and particle size distribution of the negative electrode active material, and the porosity. "Tortuosity" is a dimensionless parameter.

[0175] In the present application, the tortuosity value of the negative electrode active layer can be calculated by the following test and analysis method: the ion diffusion impedance Rion inside the pores of the negative electrode plate is tested by a symmetrical battery, and the tortuosity τ of the negative electrode active layer is calculated based on the porosity ε, the thickness d of the negative electrode active layer and the electrolyte conductivity k.

[0176] The negative electrode sheet to be tested can be disassembled from the battery cell to obtain a negative electrode sheet sample, and the residual electrolyte needs to be cleaned and removed in advance. For example, dimethyl carbonate DMC can be used to wash the negative electrode sheet sample, and then the DMC can be dried to remove it.

[0177] In the present application, porosity, ionic resistance Rion, ionic conductivity, electrode effective area and thickness of negative electrode active layer all have well-known meanings in the art. Those skilled in the art can use conventional methods in the art to test and obtain relevant parameters ε, k, Rion, A and d, and can preferably use the methods described above.

[0178] Exemplarily, the ionic impedance Rion of the negative electrode plate can be tested by the following method: cut a negative electrode plate sample of a certain area A (that is, the effective area of ​​the electrode is A), and test the ion diffusion impedance Rion inside the pores of the plate by means of a symmetrical battery, which can be obtained by testing the EIS impedance of the plate.

[0179] In the present application, the test temperature of ε, k, and Rion can be carried out at room temperature, and unless otherwise specified, can be carried out at 20°C to 30°C (such as 25°C), and further, can be carried out at 25°C.

[0180] In some embodiments of the present application, the tortuosity τ of the negative electrode active layer is numerically equal to the value calculated according to the following formula: ε×k×Rion×A / d; wherein ε is the porosity of the negative electrode active layer at 25°C; k is the ionic conductivity of the electrolyte at 25°C, in mS / cm; Rion is the ionic resistance of the negative electrode sheet at 25°C, in Ω; A is the effective area when testing Rion, in cm 2 ; d is the total thickness of the negative electrode active layer, in μm.

[0181] In some embodiments, the average particle size of the primary particles in the negative electrode active material is 0.1μm~2μm, optionally 0.2μm~1.5μm, or 0.1μm~1μm, further 0.2μm~1μm, or any of the following values ​​or a range consisting of any two of the following values: 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc.

[0182] In the present application, unless otherwise specified, the "average particle size of primary particles" in the negative electrode active material refers to the average particle size of each primary particle of the negative electrode active material. The "particle size of primary particles" refers to the maximum diameter of the primary particles in each direction.

[0183] In the present application, unless otherwise specified, the "primary particles" in the negative electrode active material are the basic units of particles in the negative electrode active material. It is understood that there are primary particles in the negative electrode active material. In the negative electrode active material, the primary particles can be in a non-agglomerated state or can be formed into agglomerates by multiple primary particles. The non-agglomerated primary particles can be referred to as "non-agglomerated primary particles", and the agglomerates formed by multiple primary particles can be referred to as "secondary particles".

[0184] By controlling the average particle size of the primary particles in the negative electrode active material (denoted as D1) within the aforementioned range, it is possible to control the negative electrode active material to have a more suitable ion transmission path and achieve a better rate, and at the same time, better control the negative electrode interface reaction and the negative electrode film formation consumption of acetylene additives. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better coordinate the control of the structural stability of the negative electrode active layer, the internal resistance of the battery and the consumption of acetylene additives participating in the negative electrode film formation, and is more beneficial to significantly improve the room temperature performance of the acetylene additive battery system.

[0185] The particle morphology of the negative electrode active material can be used to count the particle size and average value of the primary particles in the negative electrode active material. The particle morphology of the negative electrode active material can be obtained by using a scanning electron microscope (such as ZEISS Sigma 300, JEOL scanning electron microscope, Axia ChemiSEM scanning electron microscope, etc.). The sample to be tested can be obtained by laying and sticking the powder sample of the negative electrode active material on a conductive glue. In a non-limiting manner, the SEM test can refer to JY / T(001)-1996. Randomly select one or more areas in the sample to be tested for scanning testing, and based on the SEM image at a certain magnification, count the particle size of each primary particle in the scanned area and the frequency of occurrence of different particle sizes, and then calculate the average particle size of the primary particles counted. In a non-limiting manner, the magnification of a single scanning area can be 1000X, but is not limited thereto. In order to improve the accuracy of the statistical results, multiple areas can be randomly selected for scanning.

[0186] In the present application, unless otherwise specified, the maximum diameter of the primary particles in each direction in the SEM morphology of the negative electrode active material is recorded as the “particle size of the primary particles in the negative electrode active material”.

[0187] In some embodiments, the negative electrode active material includes a coated negative electrode material, and the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at least in part of the negative electrode active body. It is understood that the carbon coating layer in the coated negative electrode material is different from the chemical composition of the negative electrode active body. The negative electrode active body can select at least one material suitable for negative electrode active materials known in the art. Without limitation, the negative electrode active body can include one or more of graphite and silicon-based materials. Without limitation, graphite can include one or more of natural graphite and artificial graphite. Without limitation, the silicon-based material can include one or more of elemental silicon, silicon oxide, silicon-carbon composite material, silicon-nitrogen composite material and silicon alloy. Without limitation, the carbon coating layer in the coated negative electrode material can include one or more of soft carbon, hard carbon and amorphous carbon. Without limitation, the average thickness of the carbon coating in the coated negative electrode material can be 1nm~500nm, optionally 100nm~500nm, and further optionally 100nm~200nm. In a non-limiting manner, the mass percentage of the coating layer in the coated active material is 0.2% to 5%, and may be 0.5% to 3%.

[0188] "Soft carbon" and "hard carbon" have well-known meanings in the art. Soft carbon can be graphitized after further high-temperature treatment, while hard carbon is difficult to graphitize even after further high-temperature treatment. In this application, unless otherwise specified, "amorphous carbon" refers to a transitional carbon material with a very low degree of graphitization crystallization and a nearly amorphous form (or without a fixed shape and periodic structural regularity).

[0189] In some embodiments, the carbon coating layer in the coated negative electrode material is one of a soft carbon coating layer, a hard carbon coating layer and an amorphous carbon coating layer. It can be understood that the material composition of the soft carbon coating layer is mainly soft carbon, the material composition of the hard carbon coating layer is mainly hard carbon, and the material composition of the amorphous carbon coating layer is mainly amorphous carbon.

[0190] In some embodiments, the negative electrode active material includes a coated negative electrode material, the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at least in part of the negative electrode active body, the negative electrode active material D v 50 is 5μm~14μm, and can also be any of the following values ​​or a range consisting of any two of the following values: 5μm, 5.5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, etc.

[0191] In some embodiments, the negative electrode active material includes a coated negative electrode material, the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at at least a portion of the negative electrode active body, the average particle size of the primary particles in the negative electrode active material is 0.1μm~1.6μm, and can also be any of the following values ​​or a range selected from any two of the following values: 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, etc.

[0192] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:

[0193] (a1) The mass proportion of the coated negative electrode material in the negative electrode active material can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.;

[0194] (a2) The coated negative electrode material includes coated graphite, and the negative electrode active body in the coated graphite includes a graphite body. Without limitation, the mass proportion of the coated graphite in the negative electrode active material can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0195] In the present application, "coated graphite" is a coated negative electrode material, in which the negative electrode active body includes a graphite body; the coated graphite includes a graphite body and a carbon coating layer located on at least a portion of the surface of the graphite body.

[0196] In the present application, a "graphite body" consists of graphite.

[0197] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the lithium ion transmission channel on the surface of the negative electrode active material can be optimized, lithium ion transmission can be promoted, and the dynamics of lithium-ion secondary batteries can be improved. At the same time, it is also beneficial to inhibit negative electrode interface side reactions and inhibit the increase in negative electrode interface impedance caused by the participation of acetylene additives in negative electrode film formation, which is beneficial to better improve the room temperature performance of acetylene additive battery systems.

[0198] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the rate performance can be optimized by combining a relatively small average primary particle size (such as D1 of 0.1 μm to 1.6 μm).

[0199] In some embodiments, the coated negative electrode material is coated graphite, and the negative electrode active body is a graphite body.

[0200] In some embodiments, the porosity of the negative electrode active layer is 14% to 26%, optionally 15% to 25%, further optionally 18% to 22%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, etc.

[0201] In this application, "porosity" has a well-known meaning in the art. The "porosity" of the negative electrode active layer refers to the proportion of the pore volume in the negative electrode active layer to the total volume, which can be expressed as a percentage. The "porosity" of the negative electrode sheet can be recorded as ε.

[0202] The porosity of the negative electrode active layer can be measured by instruments and methods known in the art, for example, the AccuPyc II 1340 fully automatic true density tester of Micromeritics, USA, can be used to test the method for measuring the apparent density, true density and porosity of iron ore with reference to the national standard GB / T 24586-2009. The method includes cutting 30 small discs with a diameter of 14 mm from the negative electrode sheet, and based on the principle of gas adsorption, using an inert gas such as helium or nitrogen as a medium, testing the true volume of the 30 small discs with a diameter of 14 mm, and then calculating the relationship between the apparent volume and the true volume of the negative electrode sheet based on the area, thickness and number of the small discs to calculate the porosity of the negative electrode active layer.

[0203] The gas replacement method can also be used to obtain the porosity ε test value of the negative electrode active layer. Using the small molecule inert gas (such as He) replacement method, combined with Archimedes principle and Bohr's law, the real volume V1 of the negative electrode active layer is accurately measured, and then the apparent volume of the negative electrode active layer is calculated through testing to obtain V2 (V2 is calculated based on the area of ​​the negative electrode active layer multiplied by the thickness d of the negative electrode active layer), then the porosity = (V2-V1) / V2×100%.

[0204] True volume V1 test: Place the sample cup containing the negative electrode in the true density tester, close the test system, introduce helium according to the procedure, detect the pressure of the gas in the sample chamber and expansion chamber, and then calculate the true volume according to Bohr's law (PV=nRT).

[0205] By controlling the porosity (ε) of the negative electrode active layer within the aforementioned range, the tortuosity of the negative electrode plate can be adjusted, which is beneficial for providing a better lithium ion liquid phase transmission channel, and is also beneficial for achieving better electrolyte infiltration. It can also take into account the electrical contact network between the negative electrode active materials, which is beneficial for comprehensively improving the negative electrode kinetics and cycle performance.

[0206] In some embodiments, the active specific surface area of ​​the negative electrode active material is 2 m 2 / g~6m 2 / g, optional 2.5m 2 / g~5.5m 2 / g, further optional 3m 2 / g~5m 2 / g, can also be any of the following values ​​or a range consisting of any two of the following values: 2 m 2 / g, 2.2 m 2 / g, 2.4 m 2 / g, 2.5 m 2 / g, 2.6 m 2 / g, 2.8 m 2 / g, 3 m 2 / g, 3.5 m 2 / g, 4m 2 / g, 4.5 m 2 / g, 5 m 2 / g, 5.5 m 2 / g, 5.8 m 2 / g, 6 m 2 / g, etc.

[0207] In this application, unless otherwise specified, the "active specific surface area" of the negative electrode active material is a different concept from the "specific surface area" of the traditional negative electrode active material. The "specific surface area" of the traditional negative electrode active material is usually obtained by the gas adsorption BET method, which represents the physical adsorption specific surface area of ​​the negative electrode active material. The active specific surface area of ​​the negative electrode active material corresponds to the active specific surface area of ​​the negative electrode active material during the actual reaction, which can more accurately characterize the number of active sites of the negative electrode active material during charging and discharging. Among them, the larger the active specific surface area of ​​the negative electrode active material, the more active sites in the negative electrode active material, the faster the speed of charge exchange between active ions and electrons, and the better the kinetic performance of the negative electrode sheet and the battery.

[0208] The physical adsorption specific surface area (i.e. BET) of the negative electrode active material may have a certain influence on the active specific surface area of ​​the negative electrode active material, but it is not absolute and is also affected by the type of negative electrode active material. Generally speaking, for negative electrode active materials of the same material, the active specific surface area of ​​the negative electrode active material increases with the increase of the physical adsorption specific surface area of ​​the negative electrode active material. In addition, the larger the physical adsorption specific surface area of ​​the negative electrode active material, the higher the electrochemical activity of the negative electrode active material, and the faster the charge exchange between active ions and electrons on its surface, but at the same time, there will be more side reactions between the negative electrode active material and the electrolyte.

[0209] Exemplarily, the active specific surface area of ​​the negative electrode active material may be tested by the following method.

[0210] (1) Extract the negative electrode active material sample and reconstruct it into the electrode to be tested.

[0211] Disassemble the negative electrode sheet obtained from the battery cell, and use a solvent (such as DMC, etc.) to clean the sheet to remove residual electrolyte; extract the powder sample of the negative electrode active layer, and resuspend it in deionized water to form a uniform slurry, which is recorded as the resuspended slurry. Apply the resuspended slurry to one side of the negative electrode current collector copper foil, dry it, cold press it, and punch it into an area of ​​S0 (such as 1540.25mm 2 ) as the electrode to be tested; the single-side coating surface density and compaction density of the electrode to be tested are the same as those in Example 1. The mass M of the negative electrode active layer J =M B -M0, where M B is the mass of the electrode to be tested, and M0 is the mass of the empty current collector foil.

[0212] (2) With the electrode to be tested as the cathode and the metal lithium sheet as the anode, add ferrocene at a concentration of 50 mmol / L to the electrolyte (the same as the electrolyte in Example 1), and then assemble into a button half-cell. Take 4 parallel samples and scan them at scan rates v of 0.1 mV / s, 0.3 mV / s, 0.5 mV / s, and 1 mV / s, respectively, to obtain cyclic voltammetry curves at different scan rates, and use EC-Lab software to extract the peak current ip of the cyclic voltammetry curve. With the square root of the scan rate v as the horizontal coordinate and the peak current ip as the vertical coordinate, make a linear graph of the cyclic voltammetry curve ip and the square root of the scan rate v, and obtain its slope K. According to the Randles-Sevick equation, the slope is, where n represents the number of electron transfers, which is related to the type of probe molecule and is taken as 1 here; c represents the concentration of ferrocene, which is taken as 50 mmol / L; D is the diffusion coefficient of ferrocene, which is taken as 2.1×10 -6 cm 2 / s; then the active surface area of ​​the electrode to be tested is A = K / (2.69×10 5 ×n 2 / 3 cD1 / 2 ), the active surface area A of the negative electrode sheet and the mass M of the negative electrode active layer J The ratio can be recorded as the active specific surface area of ​​the negative electrode active material sample to be tested.

[0213] In some embodiments, the additive further includes an additive B, and the additive B is one or more of a lithium salt additive and a phosphate ester additive. In a non-limiting manner, the mass ratio of the additive B to the acetylene additive may be greater than 0 and less than or equal to 100, or greater than 0 and less than or equal to 50, or 0.1 to 100, or 0.3 to 50, or further 0.3 to 20, or 0.08 to 100, or 0.08 to 50, or further 0.08 to 20, or any of the following values ​​or a range consisting of any two of the following values: 0.05, 0.08, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, etc.

[0214] The negative electrode film formation impedance of lithium salt additives and phosphate additives is low. By introducing one or more of lithium salt additives and phosphate additives into the electrolyte, it is beneficial to reduce the impedance of the negative electrode SEI film and reduce the internal resistance of the battery; further, by controlling the mass ratio of additive B to acetylene additives within the aforementioned range, the room temperature performance of the acetylene additive battery system can be better improved.

[0215] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0216] (b1) the mass ratio of additive B to acetylene additive is 0.08 to 20, and can also be selected from any suitable value or range in the context;

[0217] (b2) The lithium salt additive includes one or more of oxalate lithium salts, lithium tetrafluoroborate, lithium difluorophosphate, fluorosulfonic acid lithium salts and lithium perchlorate; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate and lithium bisoxalatoborate; the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethanesulfonate;

[0218] (b3) Phosphate ester additives include one or more of silicon-based phosphate ester additives and alkylphosphonate ester additives; silicon-based phosphate ester additives include one or more of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)phosphite;

[0219] (b4) additives include lithium salt additives. Without limitation, the mass proportion of the lithium salt additive in the electrolyte can be greater than 0 and less than or equal to 3%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.;

[0220] (b5) Additives include phosphate additives. The mass proportion of the phosphate additives in the electrolyte can be greater than 0 and less than or equal to 1%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, etc.

[0221] In some embodiments, the negative electrode active material includes a silicon-based material.

[0222] Without limitation, the mass proportion of the silicon-based material in the negative electrode active material can be 0-40%, further optionally 0-30%, further optionally 0-25%, further optionally 0-20%, further optionally 0-10%, further optionally 0-5%, further optionally 0-3%, further optionally 0.1%-3%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0 .12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 4%, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.

[0223] Without limitation, the mass proportion of silicon-based materials in the negative electrode active material can be 0.01%~3%, optionally 0.1%~3%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.

[0224] Without limitation, the mass proportion of carbon-based materials in the negative electrode active material can be 60% to 100%, optionally 70% to 100%, further optionally 80% to 100%, further 90% to 100%, further 97% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0225] In some embodiments, the negative electrode active material includes graphite, and further, the graphite may include one or more of artificial graphite and natural graphite.

[0226] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:

[0227] (c1) The mass proportion of the silicon-based material in the negative electrode active material can be 0-3%. Optionally, the negative electrode active material includes the silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is greater than 0 and less than or equal to 3% (see also the appropriate numerical value or range in any embodiment of the context). Exemplarily, the mass proportion of the silicon-based material in the negative electrode active material can also be any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04 %, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.;

[0228] (c2) the negative electrode active material includes a silicon-based material, the silicon-based material includes a silicon-carbon composite material, the silicon-carbon composite material includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; without limitation, the mass proportion of the silicon-carbon composite material in the silicon-based material may be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.;

[0229] (c3) The mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%, and can be optionally 80% to 100%. Any suitable value or range in the context of this application can also be referred to.

[0230] "Silicon-carbon composite material" is a silicon-based material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix. The silicon-carbon composite material can be obtained by a vapor deposition method. Those skilled in the art can prepare the silicon-carbon composite material by conventional methods in the art.

[0231] By controlling the content and / or type of silicon-based materials in the negative electrode active material within the aforementioned range, the expansion and contraction changes of the negative electrode can be better controlled, which is conducive to better matching the negative electrode thin coating process with the requirements for the stability of the negative electrode active layer, reducing the generation of fresh interfaces, inhibiting negative electrode interface side reactions, reducing the consumption rate of acetylene additives, and reducing the battery internal resistance growth rate, which is conducive to better improving the battery cycle life. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.

[0232] For lithium-ion secondary batteries with traditional positive electrode plates including lithium transition metal oxide positive electrode materials, on the one hand, these acid byproduct substances may destroy the positive electrode solid electrolyte interface film (CEI film) and corrode the positive electrode active material, resulting in the dissolution of transition metal ions from the positive electrode, leading to the deterioration of battery cycle performance; on the other hand, these acid byproduct substances are easy to destroy the negative electrode SEI film, exposing a fresh interface, aggravating the negative electrode interface side reactions, and also deteriorating the battery cycle performance. Among them, the dissolution of transition metal ions from the positive electrode not only affects the structural stability of the positive electrode active material, but these dissolved transition metal ions migrate to the negative electrode and deposit, and are also easy to destroy the negative electrode solid electrolyte interface film (SEI film), aggravating the negative electrode interface side reactions.

[0233] In some embodiments, the positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide-based positive electrode material.

[0234] In the present application, unless otherwise specified, "lithium transition metal oxide positive electrode material" refers to a positive electrode active material containing lithium, transition metal and oxygen. It can be seen that the lithium transition metal oxide positive electrode material includes non-lithium metal elements, and the non-lithium metal elements include transition metal elements. Non-limitingly, in the lithium transition metal oxide positive electrode material, the molar percentage of the transition metal element relative to the non-lithium metal element can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0235] In the present application, unless otherwise specified, “non-lithium metal element” refers to a metal element that is not lithium (Li) element.

[0236] In some embodiments, the lithium transition metal oxide-based cathode material has a layered crystal structure.

[0237] In some embodiments, the positive electrode active material includes a lithium transition metal oxide positive electrode material. In a non-limiting manner, the mass proportion of the lithium transition metal oxide positive electrode material in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0238] In some embodiments, the lithium transition metal oxide-based cathode material includes a lithium nickel-based oxide-based cathode material.

[0239] In this application, unless otherwise specified, "lithium nickel-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel. It is understood that the lithium nickel-based oxide positive electrode material includes lithium, non-lithium metal elements and oxygen elements; the non-lithium metal elements include nickel. Without limitation, the mass proportion of lithium nickel-based oxide positive electrode materials in the positive electrode active material is 80% to 100%, which can be 90% to 100%, and further can be 95% to 100%. It can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0240] Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.80 Co 0.15 Al 0.05 O2.

[0241] In some embodiments, the lithium transition metal oxide-based cathode material includes a lithium nickel cobalt-based oxide-based cathode material.

[0242] In some embodiments, the positive electrode active material includes a lithium nickel cobalt-based oxide positive electrode material. In a non-limiting manner, the mass proportion of the lithium nickel cobalt-based oxide positive electrode material in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0243] "Lithium nickel cobalt-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel and cobalt elements, and is also a lithium nickel-based oxide positive electrode material containing cobalt elements. It can be understood that in this application, "lithium nickel cobalt-based oxide positive electrode material" includes lithium (Li), nickel (Ni), cobalt (Co) and oxygen (O).

[0244] In some embodiments, the lithium nickel cobalt-based oxide positive electrode material may further include an M2 element, which may be a manganese (Mn) element or an aluminum (Al) element. When the M2 element is manganese (Mn), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt manganese-based oxide positive electrode material, which may be recorded as an NCM-based positive electrode material, and when the M2 element is aluminum (Al), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt aluminum-based oxide positive electrode material, which may be recorded as an NCA-based positive electrode material.

[0245] In some embodiments, the positive electrode active material includes a lithium nickel cobalt manganese based oxide type positive electrode material.

[0246] In this application, unless otherwise specified, "lithium nickel cobalt manganese-based oxide positive electrode material" refers to a lithium transition metal oxide positive electrode material containing nickel, cobalt and manganese, and is also a lithium nickel-based oxide positive electrode material containing cobalt and manganese, and is also a lithium nickel cobalt-based oxide positive electrode material containing manganese. It can be understood that the lithium nickel cobalt manganese-based oxide positive electrode material includes lithium, non-lithium metal elements and oxygen elements; the non-lithium metal elements include nickel, cobalt and manganese. Non-limitingly, the mass proportion of lithium nickel cobalt manganese-based oxide positive electrode material in the positive electrode active material is 80% to 100%, which can be 90% to 100%, and further can be 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0247] In some embodiments, the lithium transition metal oxide positive electrode material includes a ternary positive electrode material, which may be a ternary positive electrode material. In the present application, the "ternary positive electrode material" is composed of Li element, nickel element, cobalt element, M2 element and oxygen element; wherein the M2 element may be a manganese element or an aluminum element. When the M2 element is manganese (Mn), the ternary positive electrode material is lithium nickel cobalt manganese oxide, which may be recorded as NCM, and when the M2 element is aluminum (Al), the ternary positive electrode material is lithium nickel cobalt aluminum oxide, which may be recorded as NCA.

[0248] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide positive electrode material; the thickness of the positive electrode active layer on a single side of the positive electrode current collector is less than or equal to 50 μm, and the thickness of the positive electrode active layer on a single side of the positive electrode current collector can also be any of the following thicknesses or a range selected from any two of the following thicknesses: 40 μm, 42 μm, 44 μm, 45 μm, 46 μm, 48 μm, 50 μm, etc. At this time, the positive electrode can provide a higher energy density, which can correspond to a thinner positive electrode active layer, and has better capacity matching with the negative electrode active layer, which is beneficial to inhibiting negative electrode lithium deposition and extending the battery cycle life, including extending the normal temperature life. The test method for the thickness of the positive electrode active layer on a single side of the positive electrode current collector is similar to the test method for the thickness of the negative electrode active layer on a single side of the negative electrode current collector.

[0249] In some embodiments, the positive electrode active material includes a lithium nickel-based oxide positive electrode material, and the lithium nickel-based oxide positive electrode material includes a lithium element, a non-lithium metal element, and an oxygen element; wherein the non-lithium metal element includes a nickel element; in the lithium nickel-based oxide positive electrode material, the ratio of the atomic molar ratio of the nickel element to the sum of the atomic molar ratios of the non-lithium metal elements is recorded as R Ni .

[0250] In some embodiments, R Ni ≥0.8, the thickness of the positive electrode active layer on one side of the positive electrode current collector is 40μm~50μm, and the thickness of the positive electrode active layer on one side of the positive electrode current collector can also be any of the following thicknesses or a range consisting of any two of the following thicknesses: 40μm, 42μm, 44μm, 45μm, 46μm, 48μm, 50μm, etc. In this case, the capacity matching of the positive electrode active layer and the negative electrode active layer is better, which is more conducive to extending the cycle life of the battery, including extending the life at room temperature.

[0251] Without limitation, R Ni It can be greater than or equal to 0.6, and can also be any of the following values ​​or a range consisting of any two of the following values: 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.92, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, etc.

[0252] Without limitation, R Ni It may be greater than or equal to 0.8, and may be any of the following values ​​or a range consisting of any two of the following values: 0.8, 0.85, 0.9, 0.92, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, etc.

[0253] In some embodiments, the lithium-ion secondary battery cell satisfies one or more of the following characteristics:

[0254] (d1) The positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide positive electrode material; in some embodiments, the mass proportion of the acetylene additive in the electrolyte is 0.02% to 1.8%, and can also be any of the following percentages or a range selected from any two of the following percentages: 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, etc.;

[0255] (d2) The negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is less than or equal to 3%, and can be selected from 0.1% to 3%, and can further be selected from 1% to 3%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25% , 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.; the acetylene additive includes a first acetylene compound; in some embodiments, the mass proportion of the first acetylene compound in the electrolyte is 0.05% to 2.5%, and can also be any of the following percentages or a range selected from any two of the following percentages: 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, etc.

[0256] Alkyne additives can adsorb transition metal ions in the electrolyte.

[0257] When the negative electrode active material includes the aforementioned content of silicon-based material, a fresh interface is generated as the volume of the negative electrode expands and contracts, which leads to interface side reactions and produces acid byproducts. The first alkynyl compound containing a Lewis base nitrogen heterocycle can be used to adsorb the acid byproducts.

[0258] In the present application, the sample to be tested of the "negative electrode active material" in the negative electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the negative electrode sheet, extracting the negative electrode active material from the negative electrode active layer of the negative electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, etc., and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests.

[0259] In the present application, the sample to be tested of the "positive electrode active material" in the positive electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the positive electrode sheet, and extracting the positive electrode active material from the positive electrode active layer of the positive electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, sintering and other methods, and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests. In addition, the powder material extracted from the positive electrode active layer can also be sintered to remove the organic components, thereby obtaining a powder sample of the positive electrode active material.

[0260] Exemplarily, the preparation of the powder sample of the positive electrode active material can be carried out by the following method: disassembling the battery, taking out the positive electrode plate, soaking and cleaning it with a solvent such as dimethyl carbonate to remove the residual electrolyte; scraping the powder material of the positive electrode active layer, using a solvent (such as N-methylpyrrolidone (NMP) etc.) to fully soak the powder material extracted from the positive electrode active layer, so that organic components such as binders are dissolved in the solvent (the dissolution can also be promoted by ultrasonic dispersion etc.), washing, filtering, collecting the solid phase, and then using the density difference to centrifuge to separate the relatively low-density conductive agent from the suspension, collecting the centrifugal precipitate to obtain the positive electrode active material to be tested.

[0261] The elemental composition of the positive electrode active material in the positive electrode active layer can be analyzed by methods known in the art, including but not limited to the following methods: inductively coupled plasma spectroscopy (ICP), X-ray diffraction (XRD), single crystal X-ray diffraction (SCXRD), energy dispersive spectrometer (EDS), etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the characteristics of the sample. The ICP method can be used to perform quantitative test analysis of the content of the components in the positive electrode active material.

[0262] To detect the positive electrode active material in the positive electrode active layer, after the battery is fully discharged, the battery cell is disassembled, the positive electrode plate is taken out, the material of the positive electrode active layer is scraped, and the type and proportion of elements are tested and analyzed using elemental analysis methods such as inductively coupled plasma (ICP) spectroscopy, thereby confirming the elemental composition and chemical formula of the positive electrode active material.

[0263] In some embodiments, the positive electrode active material includes a positive electrode active body and a coating layer located on at least a portion of the surface of the positive electrode active material.

[0264] For positive electrode active materials or negative electrode active materials including a coating layer (an example of a coating layer is a carbon coating layer), the cross-section can be cut using FIB (focused ion beam) and the particle cross-sectional morphology can be observed under TEM (transmission electron microscope). A clear boundary can be observed at the coating interface, and the thickness and average thickness of the coating layer can be analyzed and calculated based on the TEM image. Further combined with one or more methods such as energy dispersive spectroscopy (EDS) analysis and Raman spectroscopy, the types of substances in the coating layer and the positive electrode active body can be confirmed, or the types of substances in the coating layer and the negative electrode active body can be confirmed.

[0265] Those skilled in the art can identify the components in the positive electrode active layer and the negative electrode active layer by one or more of the following detection methods known in the art, including but not limited to: Fourier transform infrared (FT-IR) spectroscopy, ultraviolet spectroscopy, nuclear magnetic resonance spectroscopy (HNMR), 1 H NMR) method, gel permeation chromatography (GPC) method, high performance liquid chromatography (HPLC) method, mass spectrometry, X-ray photoelectron spectroscopy (XPS) method, X-ray diffraction (XRD) method, Raman spectroscopy (Raman) method, single crystal X-ray diffraction (SCXRD) method, inductively coupled plasma spectroscopy (ICP) method, energy dispersive spectrometer (EDS) analysis, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics.

[0266] As a non-limiting example, EDS can be used to distinguish carbon from silicon, and then to distinguish carbon-based materials from silicon-based materials. For another example, EDS can be used to detect the type and content of the conductive agent, but is not limited thereto.

[0267] Taking the negative electrode active material including natural graphite and artificial graphite as a non-limiting example, natural graphite and artificial graphite can be distinguished by the appearance morphology of the particles; X-ray diffraction (XRD) analysis test can be further performed. In the XRD spectrum, if the characteristic peak near 2θ 26.5° is very sharp and has a high intensity, it is natural graphite; if the characteristic peak near 2θ 26.5° is relatively wide and has a weak intensity, it is artificial graphite.

[0268] Taking the negative electrode active materials including graphite and soft carbon as an example, Raman spectroscopy can be used to distinguish graphite and soft carbon; in more detail, the characteristic peak information of the carbon component in the spectrum (such as the intensity ratio of D peak / G peak, I D / G ) to analyze soft carbon. Both D peak and G peak are Raman characteristic peaks of carbon atom crystal. D peak represents the defects of carbon atom crystal. The more defects there are, the greater the intensity of D peak is. The intensity of D peak can reflect the content of amorphous (turbostratified stacking) area. G peak represents the in-plane stretching vibration of sp2 hybridization of carbon atoms. The intensity of G peak can reflect the content of graphitized (layered structure) area. As the degree of disorder of carbon atoms increases, the intensity ratio of D peak to G peak also increases. You can also compare Raman spectra I D / G Standard Raman spectrum of graphite I D / G The difference between the D peak and the G peak in the Raman spectrum can be used to distinguish between graphite and hard carbon. Similarly, the difference between the D peak and the G peak in the Raman spectrum can be used to distinguish between natural graphite and artificial graphite.

[0269] In some embodiments, the mass proportion of acetylene additives in the electrolyte is 0.001%~3.2%, which can be optionally 0.01%~1.8%, or any of the following percentages or a range consisting of any two of the following percentages: 0.001%, 0.005%, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, etc.

[0270] By controlling the mass proportion of acetylene additives in the electrolyte within the aforementioned range, the acetylene additives can continue to play a role in repairing the SEI film during the cycle process, which is more conducive to extending the battery cycle life, including extending the life at room temperature.

[0271] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0272] (e1) The molecular weight of the acetylene additive is less than or equal to 500 Da;

[0273] (e2) The carbon-carbon triple bond in acetylenic additives is CH≡C-;

[0274] (e3) The sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive may be 75% to 100%, further may be 80% to 100%, and may also be selected from any suitable value or range in the context of the present application;

[0275] (e4) The mass proportion of the first acetylenic compound in the acetylenic additive is 75% to 100%, and can further be 80% to 100%, and can also be selected from any suitable value or range in the context of the present application.

[0276] In some embodiments, the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is greater than 50%, and may be 75% to 100%, further 80% to 100%, further 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0277] In some embodiments, the mass proportion of the first acetylenic compound in the acetylenic additive can be 75% to 100%, further can be 80% to 100%, further can be 90% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0278] In some embodiments, the mass proportion of the second alkynyl compound in the acetylene additive can be 75% to 100%, further can be 80% to 100%, further can be 90% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0279] In some embodiments, the acetylene additive is a combination of a first acetylene compound and a second acetylene compound. Further, the acetylene additive may be the first acetylene compound.

[0280] In some embodiments, the electrolyte satisfies one or more of the following characteristics:

[0281] (f1) the molecular weight of the acetylene additive is less than or equal to 300 Da;

[0282] (f2) The Lewis base nitrogen heterocycle is a substituted or unsubstituted imidazole group, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 Alkyl, cyano (-CN) or fluorine atom;

[0283] (f3) the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 90% to 100%, and can also be selected from any suitable value or range in the context of the present application;

[0284] (f4) The mass proportion of the first acetylenic compound in the acetylenic additive is 90% to 100%, and can also be selected from any suitable value or range in the context of the present application.

[0285] In this application, the term “C 1-3 "Alkylene", unless otherwise specified, may be methylene, ethylene or propylene, and may further be methylene, 1,2-ethylene or 1,3-propylene.

[0286] In this application, the term “C 1-3 "Alkyl", unless otherwise specified, may be methyl, ethyl or propyl, and may further be methyl, ethyl, n-propyl or isopropyl.

[0287] In some embodiments, R2 in the second alkynyl compound is methyl.

[0288] In some embodiments, the first alkynyl compound includes Compound II, and further may be Compound II.

[0289] In some embodiments, the second alkynyl compound includes compound III, and further can be compound III.

[0290] In some embodiments, the acetylene additive includes one or more of Compound II and Compound III;

[0291] The structure of compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;

[0292] The structure of compound III is Among them, L 21 C 1-3 Alkylene, R2 is C 1-3 alkyl.

[0293] In some embodiments, L in Compound II 11 For methylene.

[0294] In some embodiments, p2 in Compound II is 0.

[0295] In some embodiments, L in Compound III 21 For methylene.

[0296] In some embodiments, R2 in compound III is methyl.

[0297] In some embodiments, the sum of the mass proportions of Compound II and Compound III in the acetylene additive can be 75% to 100%, further optionally 80% to 100%, further 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0298] In some embodiments, the mass proportion of compound II in the acetylene additive or the first acetylenic compound can be 75% to 100%, further optionally 80% to 100%, further 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0299] In some embodiments, the mass proportion of compound III in the acetylene additive or the second acetylene compound can be 75% to 100%, further optionally 80% to 100%, further 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 75%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.

[0300] In some embodiments, Compound II is .

[0301] In some embodiments, compound III is .

[0302] By controlling the molecular weight of the acetylene additive within the aforementioned lower range, the acetylene additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and better controlling the internal resistance of the battery.

[0303] The first acetylenic compound includes both a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, which can promote the formation of an organic / inorganic dual-property interface film in the process of participating in the negative electrode interface reaction, thereby improving the stability of the negative electrode SEI film; the Lewis base nitrogen heterocycle can also absorb acid byproducts in the electrolyte, which is beneficial to improving the stability of the negative electrode interface and the negative electrode active material, and is beneficial to reducing the consumption rate of acetylene additives and reducing the growth rate of battery internal resistance; based on the aforementioned multiple effects, but not limited to the aforementioned mechanism, it is beneficial to better improve the room temperature performance of the acetylene additive battery system.

[0304] An example of a Lewis base nitrogen heterocycle is the imidazole ring in compound II.

[0305] In some embodiments, the acetylene additive includes compound II. Without limitation, the mass proportion of compound II in the acetylene additive can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0306] In some embodiments, the acetylene additive comprises a structure of Compound IIa, without limitation, the mass proportion of compound IIa in the acetylene additive can be 80% to 100%, optionally 90% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.

[0307] In some embodiments, the non-aqueous solvent includes a linear carbonate.

[0308] In the present application, unless otherwise specified, "chain carbonate" refers to a chain compound having a *-OC(=O)-O-* structure, where two *s each independently represent a bonding site to a carbon atom.

[0309] In some embodiments, the structure of the linear carbonate is R 21 -OC(=O)-OR22 , R 21 and R 22 Each is independently a chain alkyl group having 1 to 4 (can be 1, 2, 3 or 4) carbon atoms. 21 and R 22 Each is independently methyl, ethyl or propyl. 21 and R 22 Each is independently methyl or ethyl.

[0310] In some embodiments, the non-aqueous solvent includes dimethyl carbonate. Without limitation, the mass proportion of dimethyl carbonate in the non-aqueous solvent is greater than or equal to 20%, optionally 20% to 50%, and further optionally 20% to 40%.

[0311] In some embodiments, the non-aqueous solvent includes a linear carboxylate compound.

[0312] In this application, unless otherwise specified, "chain carboxylate" refers to a chain compound having a *-C(=O)-O-* structure, where two *s each independently represent a bonding site with a carbon atom. Chain carboxylate compounds used in electrolytes for lithium-ion secondary batteries generally have a lower viscosity, which is beneficial to improving the lithium ion conductivity of the electrolyte.

[0313] In some embodiments, the ionic conductivity of the electrolyte at 25°C is greater than or equal to 9 mS / cm, and can be selected from 9 mS / cm to 20 mS / cm, and can be further selected from 10 mS / cm to 18 mS / cm. It can also be any of the following conductivities or a range consisting of any two of the following conductivities: 9 mS / cm, 10 mS / cm, 11 mS / cm, 12 mS / cm, 13 mS / cm, 14 mS / cm, 15 mS / cm, 16 mS / cm, 18 mS / cm, 20 mS / cm, etc.

[0314] In this application, unless otherwise specified, the "ionic conductivity" of the electrolyte has a well-known meaning in the art, and can be tested and analyzed using existing methods in the art. The ionic conductivity can be obtained by testing with a conductivity tester, such as a DDSJ-318 conductivity meter. The test temperature can be 25±0.1°C. The test can be performed with reference to the method of HG / T 4067-2015. Unless otherwise specified, the unit of the ionic conductivity of the electrolyte is millisiemens / cm (mS / cm).

[0315] Unless otherwise specified, the following steps may be used for testing:

[0316] Pretreatment: Take the standard liquid and keep it at a constant temperature of 25℃ (deviation ±0.1℃), and take the test liquid and keep it at a constant temperature of the test temperature (deviation ±0.1℃);

[0317] Test: Test the instrument with two standard solutions at 25°C. After calibration, clean the electrode and place the test sample electrode vertically into the liquid to be tested. Click to start the test and wait for the data to stabilize for more than 10 seconds to record the test results.

[0318] The following is some description about the positive electrode.

[0319] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer includes a positive electrode active material.

[0320] Without limitation, the weight percentage of the positive electrode active material in the positive electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0321] As a non-limiting example, the positive electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the positive electrode active layer is disposed on any one or both of the two surfaces of the positive electrode current collector that are opposite to each other.

[0322] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. In the positive electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. In the positive electrode current collector, the composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Non-limitingly, in the positive electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0323] The positive electrode active material may be a positive electrode active material for a battery known in the art. These positive electrode active materials may be used alone or in combination of two or more.

[0324] The type of positive electrode active material in the positive electrode sheet can refer to the description in the context of this application. Without limitation, other types of positive electrode active materials can also be introduced into the positive electrode active material. Other types of positive electrode active materials can include lithium-containing phosphate active materials.

[0325] In some embodiments, the positive electrode active material includes a lithium-containing phosphate-based positive electrode material.

[0326] Without limitation, the mass proportion of lithium phosphate positive electrode materials in the positive electrode active material is 0%~5%, which can be optionally 0.1%~5%, or can be any of the following percentages or a range composed of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0327] In this application, unless otherwise specified, "lithium-containing phosphate positive electrode material" refers to a type of positive electrode active material containing iron-lithium phosphate components, and further refers to a positive electrode active material containing lithium elements, transition metal elements and phosphate ions (PO4 3- ) positive electrode active material. Unless otherwise specified, the "lithium-containing phosphate positive electrode material" may be an olivine structure.

[0328] In some embodiments, the positive electrode active material includes an olivine structured lithium phosphate-based positive electrode material. Non-limiting examples of olivine structured lithium phosphate-based positive electrode materials may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. An example of lithium iron phosphate is LiFePO4. An example of lithium manganese phosphate is LiMnPO4.

[0329] A non-limiting example of the lithium-containing phosphate-based positive electrode material is a lithium iron phosphate-based positive electrode material.

[0330] In this application, unless otherwise specified, "iron lithium phosphate positive electrode material" refers to a type of positive electrode active material containing iron lithium phosphate components. Unless otherwise specified, the "iron lithium phosphate positive electrode material" may be an olivine structure.

[0331] In some embodiments, the positive electrode active material includes a lithium iron phosphate positive electrode material. Further, the lithium iron phosphate positive electrode material may include at least one of lithium iron phosphate and a composite material of lithium iron phosphate and carbon.

[0332] In some embodiments, the composite material of lithium iron phosphate and carbon is carbon-coated lithium iron phosphate.

[0333] In some embodiments, the lithium iron phosphate-based cathode material includes carbon-coated lithium iron phosphate.

[0334] In the present application, the term "carbon-coated lithium iron phosphate" includes a lithium iron phosphate body and a carbon coating layer located on at least a portion of the surface of the lithium iron phosphate body, and the lithium iron phosphate body contains lithium iron phosphate. Without limitation, the carbon coating layer in the carbon-coated lithium iron phosphate may include one or more of soft carbon, hard carbon and amorphous carbon. Without limitation, the mass proportion of the carbon coating layer in the lithium iron phosphate positive electrode material may be 1% to 1.5%.

[0335] In some embodiments, the lithium iron phosphate positive electrode material includes a lithium iron phosphate-based positive electrode material. The lithium iron phosphate-based positive electrode material refers to a type of positive electrode active material containing a lithium iron phosphate component.

[0336] In some embodiments, the lithium iron phosphate body includes lithium iron phosphate.

[0337] In some embodiments, the lithium iron phosphate-based positive electrode material includes carbon-coated lithium iron phosphate. In this case, the carbon-coated lithium iron phosphate includes carbon-coated lithium iron phosphate.

[0338] In the present application, the term "carbon-coated lithium iron phosphate" includes lithium iron phosphate and a carbon coating layer located at least on a portion of the surface of the lithium iron phosphate. Further, the carbon coating layer may include one or more of soft carbon, hard carbon and amorphous carbon.

[0339] In some embodiments, the carbon coating layer in the carbon-coated lithium iron phosphate includes soft carbon. In some embodiments, the carbon coating layer is a soft carbon coating layer, in which case the carbon-coated lithium iron phosphate can be recorded as soft carbon-coated lithium iron phosphate. "Soft carbon coating layer" refers to a coating layer mainly composed of soft carbon, and the mass proportion of soft carbon in the coating layer can be close to 100%. The mass proportion of soft carbon in the soft carbon coating layer in the carbon-coated lithium iron phosphate can be 1% to 1.5%, optionally 1.4% to 1.5%, but is not limited thereto.

[0340] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode sheet is different when the battery is discharged to different states. In the exemplary description of the positive electrode active material in this application, unless otherwise specified, the content of Li can be the initial state of the material or the non-initial state after the charge and discharge cycle. The positive electrode active material is applied to the positive electrode in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material at the positive electrode usually changes. Among them, the content of Li can be measured by atomic molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before being made into a positive electrode active layer. It can be understood that the new material or new substance obtained by appropriately modifying the listed positive electrode active materials is also within the scope of the positive electrode active material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include one or more of coating modification and doping modification.

[0341] In the exemplary description of the positive electrode active material in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the atomic molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by atomic molar content, but is not limited to this.

[0342] In some embodiments, the positive electrode active layer may optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. Typically, the weight percentage of the binder in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 1 wt% to 5 wt%, based on the total weight of the positive electrode active layer.

[0343] In some embodiments, the positive electrode active layer optionally includes a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Typically, the weight percentage of the conductive agent in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 0 to 5 wt%, based on the total weight of the positive electrode active layer.

[0344] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Further, the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. Cold pressing can be performed by a cold rolling mill. The type of solvent in the positive electrode slurry can include but is not limited to any of the aforementioned embodiments, for example, it can include N-methylpyrrolidone (NMP), and further can be NMP. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector, or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s.

[0345] In some embodiments, the positive electrode active material includes a lithium transition metal oxide active material, and further, the mass proportion of the lithium transition metal oxide active material in the positive electrode active material can be greater than or equal to 50%, but is not limited thereto. When the positive electrode slurry is coated, the coating surface density (measured by the coating surface density on both sides of the positive electrode current collector) on a dry weight basis (excluding the solvent) can be (0.05 ~ 0.6) g / 1540.25 mm 2 , optional: (0.1~ 0.3) g / 1540.25 mm 2 The compaction density of the positive electrode sheet can be 3.0 g / cm 3 ~ 4.2 g / cm 3 , optional 3.3 g / cm 3 ~ 3.8 g / cm 3 .

[0346] The "compacted density" used in this application has a well-known meaning in the art and is one of the reference indicators of material energy density. In this application, unless otherwise specified, the compacted density of the positive electrode sheet refers to the ratio of the mass of the positive electrode active layer to its volume, and the compacted density of the negative electrode sheet refers to the ratio of the mass of the negative electrode active layer to its volume.

[0347] The following are some additional descriptions about the negative electrode.

[0348] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material.

[0349] Without limitation, the weight percentage of the negative electrode active material in the negative electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.

[0350] As a non-limiting example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active layer is disposed on any one or both of the two surfaces facing each other of the negative electrode current collector.

[0351] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. In the negative electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. In the negative electrode current collector, the composite current collector may be formed by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In a non-limiting manner, in the negative electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0352] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials or substances, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0353] In some embodiments, the negative electrode active layer may optionally include a binder. Without limitation, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). Without limitation, the weight percentage of the binder in the negative electrode active layer may be 0wt% to 20wt%, further 0wt% to 10wt%, further 0 to 5wt%, further 1wt% to 5wt%, and further 1wt% to 3wt%.

[0354] The type of negative electrode active material can also be referred to the context of this application.

[0355] In some embodiments, the negative electrode active layer may optionally include a conductive agent. In a non-limiting manner, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In a non-limiting manner, the weight percentage of the conductive agent in the negative electrode active layer may be 0wt% to 15wt%, further optionally 0wt% to 10wt%, and further optionally 0wt% to 5wt%.

[0356] In some embodiments, the negative electrode active layer may optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). In a non-limiting manner, the weight percentage of other additives in the negative electrode active layer may be 0 wt% to 15 wt%, further 0 wt% to 10 wt%, further 0 wt% to 5 wt%, further 0 wt% to 3 wt%, and further 0 wt% to 2 wt%.

[0357] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry. Further, the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. Cold pressing can be performed using a cold rolling mill. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 30 wt%~70wt%, optionally 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000 mPa·s~10000 mPa·s, optionally 3000 mPa·s~10000 mPa·s. The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 2.0 g / cm 3 , optional 1.0 g / cm 3 ~ 1.8 g / cm 3 .

[0358] The electrolyte is exemplarily described below.

[0359] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The electrolyte includes electrolyte salt and solvent.

[0360] In some embodiments, the electrolyte is a non-aqueous electrolyte. The non-aqueous electrolyte may include an electrolyte salt and a non-aqueous solvent.

[0361] The electrolyte salt of the non-aqueous solvent in the electrolyte solution can refer to the description above and below this application.

[0362] In some embodiments, the electrolyte salt includes an electrolyte lithium salt, and may further be an electrolyte lithium salt. Without limitation, other types of electrolyte salts may also be introduced into the electrolyte.

[0363] In some embodiments, the molar volume concentration of the electrolyte salt in the electrolyte can generally be 0.5 mol / L~5 mol / L, optionally 0.6 mol / L~1.8 mol / L, optionally 0.7 mol / L~1.2 mol / L, and can also be any of the following concentrations or a range consisting of any two of the following concentrations: 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, etc.

[0364] Without limitation, the electrolyte includes an electrolyte lithium salt, which may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0365] In some embodiments, the electrolyte includes one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and in some embodiments, the electrolyte includes at least lithium hexafluorophosphate.

[0366] In some embodiments, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte is 0 to 0.5 mol / L, which can be 0.01 mol / L to 0.5 mol / L, or any of the following concentrations or a range selected from any two of the following concentrations: 0 mol / L, 0.01 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.075 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, etc.

[0367] In some embodiments, the electrolyte includes lithium bis(fluorosulfonyl)imide (LiFSI), which can act as a film-forming additive and an electrolyte salt in the electrolyte. In a non-limiting manner, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte can be 0.01 mol / L to 0.5 mol / L, optionally 0.01 mol / L to 0.3 mol / L, or any of the following concentrations or a range consisting of any two of the following concentrations: 0.01 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.075 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5mol / L, etc.

[0368] In some embodiments, the electrolyte includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Without limitation, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte can be greater than 0 mol / L and less than or equal to 0.5 mol / L, and can be selected from 0.01 mol / L to 0.5 mol / L, and can also be selected from a suitable range or value in any embodiment of the context.

[0369] Lithium bis(fluorosulfonyl)imide (LiFSI) can participate in the formation of a stable solid electrolyte interface film at the positive and negative electrodes. On the one hand, by introducing LiFSI into the electrolyte, the stability of the positive and negative electrode interface films can be improved; on the other hand, LiFSI's ability to dissociate lithium ions is better than lithium hexafluorophosphate (LiPF6), so the addition of LiFSI is also beneficial to improve the liquid phase conductivity.

[0370] The type of non-aqueous solvent in the electrolyte can refer to the description in the context of this application. Without limitation, other types of non-aqueous solvents can also be introduced into the electrolyte. In some embodiments, the non-aqueous solvent can include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC, ), one or more of propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0371] The electrolyte includes additives, including at least the aforementioned acetylene additive (which may be referred to as the first additive).

[0372] The types of additives in the electrolyte can refer to the description in the context of this application. Without limitation, other types of additives can also be introduced into the electrolyte. Other types of additives can include negative electrode film-forming additives, positive electrode film-forming additives, and can also include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, etc.

[0373] In some embodiments, the additive in the electrolyte includes a second additive. In the present application, unless otherwise specified, the "second additive" is a negative electrode film-forming additive different from an acetylene additive. "Negative electrode film-forming additive" refers to an additive that can decompose at the negative electrode working potential and participate in the formation of a negative electrode SEI film. The higher the reduction potential of the negative electrode film-forming additive, that is, relative to Li / Li +The more positive the potential value, the earlier the negative electrode film-forming additive decomposes, and the earlier it participates in the formation of the negative electrode SEI film. It is understandable that some negative electrode film-forming additives can also participate in the formation of the interface film (CEI film) at the positive electrode. Generally, those skilled in the art can judge whether a certain additive can participate in the formation of the negative electrode SEI film based on methods such as reduction potential analysis, decomposition product and SEI film component analysis, and electrochemical performance verification; illustratively, the reduction potential of the additive can be measured by cyclic voltammetry in a simulated battery environment (such as lithium metal to the working electrode); illustratively, the SEI film composition can be analyzed by chemical composition analysis methods including but not limited to X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and the like; illustratively, it can be judged whether a certain additive introduced can participate in the formation of the negative electrode SEI film based on the changes in performance indicators such as the first coulomb efficiency, cycle stability and impedance spectrum when the additive is introduced or not.

[0374] In some embodiments, the second additive includes one or more of a lithium salt additive, a phosphate ester additive, vinylene carbonate, a fluorocarbonate additive (such as fluoroethylene carbonate), a saturated sultone, a cyclic sulfate, etc.;

[0375] Without limitation, the mass ratio of the second additive to the acetylene additive can be greater than 0 and less than or equal to 100, or greater than 0 and less than or equal to 50, or 0.1-100, or 0.3-50, or 0.3-20, or 0.08-100, or 0.08-50, or 0.08-20, or any of the following values ​​or a range consisting of any two of the following values: 0.05, 0.08, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, etc.

[0376] In some embodiments, the additive in the electrolyte includes a cyclic sulfate.

[0377] In the present application, "cyclic sulfate" contains one or more monocyclic sulfate units, and "monocyclic sulfate unit" contains *-OS(=O)2-O-*, where two *s each independently represent a bonding site to a carbon atom.

[0378] In some embodiments, the additive includes a polycyclic sulfate, which contains multiple monocyclic sulfate units.

[0379] In some embodiments, multiple monocyclic sulfate units in the polycyclic sulfate are linked in a chain-like manner.

[0380] In some embodiments, the number of monocyclic sulfate units in the polycyclic sulfate is 2-4, and further can be 2, 3 or 4.

[0381] In some embodiments, the monocyclic sulfate ester unit is a 5- to 7-membered monocyclic ring, which may be a 5-membered ring, a 6-membered ring or a 7-membered ring, and may further be a 5-membered ring or a 6-membered ring.

[0382] In some embodiments, the monocyclic sulfate unit is substituted by 0, 1 or more substituent groups Q3, and the substituent groups Q3 in the monocyclic sulfate unit are each independently halogen, C 1-3 Alkyl or C 1-3 Alternatively, the substituent groups Q3 in the monocyclic sulfate unit are each independently a fluorine atom, a methyl group or a methoxy group.

[0383] By introducing cyclic sulfate into the electrolyte, the negative electrode interface film can be optimized, the stability of the negative electrode SEI film can be improved, the negative electrode interface side reactions can be reduced, and the negative electrode interface impedance and battery internal resistance can be better controlled.

[0384] In some embodiments, the additive in the electrolyte includes vinyl sulfate.

[0385] In some embodiments, the additive in the electrolyte includes vinylene carbonate. Vinylene carbonate (VC) can optimize the SEI film. By introducing VC into the electrolyte, it is beneficial to reduce or delay the consumption of the acetylene additive in the negative electrode film formation, and better control the charge transfer impedance on the negative electrode surface and the internal resistance of the battery.

[0386] In some embodiments, the additive in the electrolyte includes fluoroethylene carbonate (FEC). Fluoroethylene carbonate (FEC) can form a relatively strong interface film with low ion transfer impedance on the surface of the negative electrode at room temperature. By introducing fluorocarbonate additives (such as FEC) into the electrolyte, it is beneficial to reduce or delay the consumption of acetylene additives in the negative electrode film formation, and better control the negative electrode interface impedance and battery internal resistance.

[0387] The separator is exemplarily described below.

[0388] In some embodiments, the lithium-ion secondary battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0389] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0390] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and optionally 6 μm to 20 μm.

[0391] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0392] In some embodiments, the lithium-ion secondary battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0393] In some embodiments, the outer packaging of the lithium-ion secondary battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion secondary battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0394] One aspect of the present application also provides a lithium-ion secondary battery. The lithium-ion secondary battery includes at least one battery cell. The lithium-ion secondary battery may include one or more battery cells. Further, the battery cell is a lithium-ion secondary battery cell.

[0395] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0396] In some embodiments, the structure of a lithium-ion secondary battery cell can be referred to Figure 1 and Figure 2 .

[0397] In some embodiments, reference Figure 2, the outer packaging may include a battery case 51 and a cover plate 53. Among them, the battery case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The battery case 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs. In some embodiments, the injection coefficient of the electrolyte is greater than or equal to 1.6g / Ah.

[0398] The lithium-ion secondary battery may be a battery device 4 or a battery pack 1 .

[0399] The battery device includes at least one battery cell, and at least one battery cell is a lithium-ion secondary battery cell. The number of battery cells contained in the battery device can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery device. The number of lithium-ion secondary battery cells contained in the battery device can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery device.

[0400] Figure 3 4 is an example of a battery device. Figure 3 In the battery device 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery device 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0401] Optionally, the battery device 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0402] In some embodiments, the battery devices described above may also be assembled into a battery pack. The number of battery devices contained in the battery pack may be one or more. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0403] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery devices 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery devices 4. The plurality of battery devices 4 can be arranged in the battery box in any manner.

[0404] In a second aspect of the present application, a method for preparing a lithium ion secondary battery is provided, which can be used to prepare the lithium ion secondary battery of the first aspect of the present application.

[0405] In some embodiments, a method for preparing a lithium-ion secondary battery is provided, comprising the following steps: allowing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet to stand and soak in an electrolyte for chemical formation.

[0406] According to some embodiments of the second aspect of the present application, a method for preparing a lithium-ion secondary battery monomer is provided, which comprises the following steps:

[0407] S100: placing an electrode assembly including a positive electrode sheet and a negative electrode sheet in a battery housing; wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, the negative electrode active layer includes a negative electrode active material, the negative electrode active material includes a graphite-based material, and optionally, the mass proportion of the graphite-based material in the negative electrode active material may be 60% to 100%, and the suitable value or range described in the first aspect of the present application may also be referred to; the thickness of the negative electrode active layer on one side of the negative electrode current collector is less than or equal to 55 μm, and the D of the negative electrode active material is less than or equal to 100 μm; v 50: 3μm~15μm;

[0408] S200: injecting electrolyte into the battery housing, and allowing the electrolyte to soak the positive electrode plate and the negative electrode plate to form a battery; wherein the electrolyte includes electrolyte salt, non-aqueous solvent and additives; the additives include acetylene additives, which are compounds containing carbon-carbon triple bonds; the acetylene additives include one or more of a first acetylene compound and a second acetylene compound; optionally, the sum of the mass proportions of the first acetylene compound and the second acetylene compound in the acetylene additive is 75% to 100%, and reference may also be made to the suitable values ​​or ranges described in the first aspect of the present application.

[0409] The definitions of the first alkynyl compound and the second alkynyl compound may refer to the first aspect of the present application.

[0410] Illustratively, the first alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 It is composed of an alkylene group and -OC(=O)-R1, and R1 is a Lewis base nitrogen heterocycle.

[0411] Illustratively, the second alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-O-R2, R2 is an alkyl group, which can be C 1-3 alkyl.

[0412] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application.

[0413] In some embodiments, in step 200, after injecting electrolyte into the battery casing, a lithium-ion secondary battery assembly is obtained.

[0414] In some embodiments, the lithium-ion secondary battery assembly may correspond to a state before a formation treatment is performed.

[0415] Without limitation, the formation temperature may be 45° C., but is not limited thereto.

[0416] In some embodiments, the formation can be performed at 45° C. using a method comprising the following steps (steps S1, S2, S3 and S4 are performed in sequence):

[0417] S1) Charge at 0.05C for 14 minutes to 3V, and let stand for 10 minutes;

[0418] S2) Charge at 0.1C to 3.4V and let stand for 10 minutes;

[0419] S3) Charge at 0.2C to 3.65V and let stand for 10 minutes;

[0420] S4) Charge at 0.2C to 3.75V and let stand for 10 minutes;

[0421] End of transformation.

[0422] In the present application, the concentrations of additives and electrolyte salts involved in “injecting electrolyte into the battery casing” correspond to “initial concentrations”, which may correspond to the initial mass proportion of the additives in the electrolyte and the initial molar volume concentration of the electrolyte salt in the electrolyte, respectively.

[0423] In some embodiments, in the step of injecting electrolyte into the battery housing, the initial mass percentage of the acetylene additive in the electrolyte is 0.1%~5%, which can be optionally 0.1%~3%, or any of the following percentages or a range consisting of any two of the following percentages: 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0424] The acetylene additives involved in the present application can be purchased from the market, or synthesized using existing methods in the field of organic chemical synthesis. When the structural formula of the acetylene additive is selected, those skilled in the art can select a suitable organic synthesis method to prepare the target compound; further, those skilled in the art can also identify the structure of the prepared acetylene additive by one or more of the following detection methods, including but not limited to: nuclear magnetic resonance hydrogen spectrum ( 1 H NMR) method, high performance liquid chromatography (HPLC) method, matrix-assisted laser desorption-to-time of flight mass spectrometry (MADI-TOF) method, Fourier transform infrared (FT-IR) spectroscopy, etc.

[0425] In some embodiments, the initial mass proportion of the chain carboxylic acid ester in the electrolyte is 10% to 30%, optionally 20% to 4%, and further optionally 20% to 30%.

[0426] In some embodiments, the initial mass proportion of dimethyl carbonate in the electrolyte is greater than or equal to 20%, and can be optionally 20% to 40%.

[0427] In some embodiments, the initial mass proportion of the lithium salt additive in the electrolyte is 0.3% to 3%. Without limitation, the lithium salt additive may include one or more of oxalate lithium salts, lithium tetrafluoroborate, lithium difluorophosphate, fluorosulfonic acid lithium salts, etc.; oxalate lithium salts may include one or more of lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalate phosphate (LiDFOP), lithium tetrafluorooxalate phosphate (LiTFOP), etc.; fluorosulfonic acid lithium salts may include one or more of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.

[0428] In some embodiments, the initial mass proportion of lithium difluorophosphate in the electrolyte is 0.1% to 1%.

[0429] In some embodiments, the initial mass percentage of LiDFOB in the electrolyte is 0.05% to 1%.

[0430] In some embodiments, the initial mass proportion of the phosphate additive in the electrolyte is 0.1% to 1%. Without limitation, the phosphate additive may include a silicon-based phosphate additive; the silicon-based phosphate additive may include one or more of tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)phosphite (TMSPi), and the like.

[0431] In some embodiments, the initial mass percentage of TMSP in the electrolyte is 0.1% to 0.3%.

[0432] In some embodiments, the initial mass proportion of the cyclic sulfate in the electrolyte is 0.1% to 2%. The cyclic sulfate may be dithiothreitol (DTD).

[0433] In some embodiments, the initial mass proportion of vinylene carbonate (VC) in the electrolyte is 0.1% to 3%.

[0434] In some embodiments, the initial mass proportion of fluoroethylene carbonate (FEC) in the electrolyte is 0.1% to 3%.

[0435] In some embodiments, the initial molar volume concentration of lithium bis(fluorosulfonyl)imide (LiFSI) in the electrolyte is 0.01 mol / L to 0.5 mol / L.

[0436] Those skilled in the art know that after the chemical formation treatment, the content of some additive components in the electrolyte may change. As a non-limiting example, for example, some film-forming additive components are reduced in content due to their participation in the formation of the solid electrolyte interface film of the positive electrode and / or the negative electrode. As a non-limiting example, the content of acetylene additives in the electrolyte is generally reduced after the chemical formation treatment relative to the electrolyte before the chemical formation treatment.

[0437] In some embodiments, after the formation treatment, in the prepared lithium ion secondary battery, the content of each additive can refer to the first aspect of the present application.

[0438] In the lithium-ion secondary battery assembly, the types of electrolyte salt and non-aqueous solvent in the electrolyte can refer to the first aspect of the present application. After the chemical formation treatment, the mass proportions of the electrolyte salt and the solvent in the electrolyte may change.

[0439] In the lithium-ion secondary battery assembly, the material composition and size of the positive electrode sheet, the negative electrode sheet and the separator can refer to the first aspect of the present application. The size of the positive electrode sheet, the negative electrode sheet and the separator in the lithium-ion secondary battery assembly may be slightly different from the size in the lithium-ion secondary battery of the first aspect.

[0440] In some embodiments, the lithium-ion secondary battery monomer described in the first aspect of the present application is prepared.

[0441] In some embodiments, in the prepared lithium-ion secondary battery, the positive electrode active material includes a lithium nickel-based oxide positive electrode material, the lithium nickel-based oxide positive electrode material contains Li element, non-lithium metal element and O element, and the non-lithium metal element includes Ni element.

[0442] In some embodiments, the positive electrode active material includes a chemical formula of Li x (Ni a Cob M’ c M’’ d )O 2-e a lithium nickel-based oxide, wherein 0.6 ≤ x ≤ 1.2, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 1 (optionally, 0 < d < 1), a + b + c + d = 1, -0.4 ≤ e ≤ 0.1 (optionally, -0.2 ≤ e ≤ 0.1, further optionally, -0.1 ≤ e ≤ 0.1). M’ may include at least one of Mn and Al. M’’ may include one or more of Na, K, Ca, Ba, Sb, Ti, Zr, W, Sr, Nb, Mo, Si, Mg, B, Cr, and Ta. The value or range of values of a can refer to R Ni The value or range of values. Without limitation, the value or range of values of b can refer to R Co In some embodiments, M’ is the Mn element.

[0443] Without limitation, x can be any one of the following values, or selected from the range formed by any two of the following values: 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, etc.

[0444] Without limitation, (2 - e) can be any one of the following values, or selected from the range formed by any two of the following values: 1.6, 1.7, 1.8, 1.9, 2, 2.05, 2.06, 2.08, 2.1, etc.

[0445] According to some embodiments of the third aspect of the present application, there is provided a battery device, which includes one or more of the lithium ion secondary battery monomers described in the first aspect of the present application and the lithium ion secondary battery monomers prepared by the preparation method of the lithium ion secondary battery monomers described in the second aspect of the present application;

[0446] In some embodiments, the battery device includes one or more lithium ion secondary battery monomers.

[0447] The number of lithium ion secondary batteries in the battery device can be controlled according to the capacity requirement.

[0448] In some embodiments of the fourth aspect of the present application, there is provided an electrical device, which includes at least one of the lithium ion secondary battery monomers described in the first aspect of the present application, the lithium ion secondary battery monomers prepared by the preparation method of the lithium ion secondary battery monomers described in the second aspect of the present application, and the battery device described in the third aspect of the present application.

[0449] In some embodiments, the electrical device includes the lithium ion secondary battery monomers of any embodiment provided by the present application.

[0450] Lithium-ion secondary battery cells can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, electric motorcycles, electric tools, etc., but are not limited thereto. The electrical device may also be used in the fields of military equipment, aerospace, etc., and may also be used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations.

[0451] As an electric device, a lithium-ion secondary battery cell can be selected according to its use requirements.

[0452] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery device or a battery pack can be used.

[0453] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a lithium-ion secondary battery cell may be used as a power source.

[0454] In a fifth aspect of the present application, a lithium-ion secondary battery assembly is provided, which is the lithium-ion secondary battery assembly in the method for preparing a lithium-ion secondary battery described in the second aspect of the present application.

[0455] Below, some embodiments of the present application are described. The described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be understood as limitations on the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0456] If the techniques or conditions are not specified in the examples, the above description, or the techniques or conditions described in the literature in the field, or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially, or can be synthesized in a conventional manner from commercially available products.

[0457] In the following examples, room temperature refers to 20°C to 30°C.

[0458] In the following examples, unless otherwise specified, the parameters involved can be confirmed by referring to the test methods described above. v 50 and D v 1 Malvern 2000 (MasterSizer 2000) laser particle size analyzer can be used for testing. The active specific surface area of ​​the negative electrode active material, the single-side thickness, porosity, tortuosity, single-side density, etc. of the negative electrode active layer can be obtained by testing using the method described above. For carbon coating, transmission electron microscope JEM-F200 combined with EDS (Energy Dispersive Spectrometer) can be used for testing. For example, for the ion conductivity test of the electrolyte, DDSJ-318 conductivity meter is used, referring to the HG-T 4067-2015 detection method. For the organic components in the prepared lithium-ion secondary battery, the organic components in the electrolyte can be qualitatively and quantitatively analyzed by gas chromatography with reference to the standard "GB / T 9722-2023 General Rules for Gas Chromatography of Chemical Reagents".

[0459] In the following embodiments, the electrolyte salt is an electrolyte lithium salt as an example, and the compound IIa is an acetylene additive as a non-limiting example.

[0460] 1. Preparation of lithium-ion secondary batteries (lithium-ion secondary battery monomers)

[0461] Example 1.

[0462] (1) Positive electrode

[0463] The positive electrode active material (NCM811), conductive agent carbon black (Super P) and binder polyvinylidene fluoride (PVDF) were mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of 95:2.5:2.5 to obtain a positive electrode slurry with a solid content of 50wt%. The positive electrode slurry was coated on both sides of the positive electrode current collector aluminum foil, and the coating surface density on both sides of the positive electrode current collector was 0.26g / 1540.25mm 2 Through drying, cold pressing, slitting, cutting and other processes, the positive electrode sheet is obtained, and the compaction density is 3.5g / cm 3 .

[0464] In this example, the D of the positive electrode active material v 50 is 3μm.

[0465] (2) Negative electrode

[0466] The negative electrode active material (coated graphite), conductive agent carbon black (Super P), styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC-Na) were mixed uniformly in a solvent deionized water at a weight ratio of 95:1.5:1.5:2 to prepare a negative electrode slurry with a solid content of 70wt%. The negative electrode slurry was coated on both sides of the negative electrode current collector copper foil (the coating weight on both sides was consistent), and the coating surface density on one side of the negative electrode current collector was 0.112g / 1540.25mm 2 , through drying, cold pressing, slitting and cutting processes, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is about 1.6g / cm 3 .

[0467] In this example, the negative electrode active material is coated graphite, including a graphite body and a soft carbon coating layer located on the surface of the graphite body. The graphite body is artificial graphite, and the soft carbon coating layer accounts for about 5% of the mass of the coated graphite.

[0468] In this example, the porosity of the negative electrode active layer is 20%, the tortuosity is 5, and the D v 50 is 4 μm, and the D v 1 is 1 μm, the average primary particle size (D1) of the negative electrode active material is in the range of 0.1 μm to 1 μm, and the active specific surface area of ​​the negative electrode active material is about 4 m 2 / g.

[0469] (3) Isolation film: conventional PE film is used as isolation film

[0470] (4) Preparation of electrolyte: Add additives to the non-aqueous solvent, mix well, then add fully dried electrolyte lithium salt, mix well to fully dissolve the electrolyte lithium salt, and prepare the electrolyte.

[0471] The electrolyte salt in the electrolyte is an electrolyte lithium salt, and further, the electrolyte lithium salt is lithium hexafluorophosphate, and the initial concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L. The non-aqueous solvent is EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) in a mass ratio of 2:3:5. The additives are 2-propynyl-1-1H-imidazole-1-carboxylate and fluoroethylene carbonate (FEC). The structure of the acetylene additive (also recorded as the first additive) is shown in formula (IIa), also recorded as compound IIa, and the initial mass proportion of compound IIa in the electrolyte is 3%.

[0472]

[0473] (5) Preparation of lithium-ion secondary batteries: stack and wind the positive electrode sheet, separator and negative electrode sheet in order to obtain a bare cell (electrode assembly); weld the tabs to the bare cell, place the bare cell into an aluminum shell, and bake it at 80°C to remove water. Then inject electrolyte and seal it. Then, go through the steps of standing, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain a lithium-ion secondary battery (lithium-ion secondary battery cell).

[0474] After injecting the electrolyte, a lithium-ion secondary battery assembly is obtained.

[0475] In this example, the static infiltration parameters are: 18 hours at room temperature and then 6 hours at 45°C.

[0476] In this example, the formation parameters are as follows: at 45°C,

[0477] 0.05C charge for 14 minutes to 3.0V, let stand for 10 minutes;

[0478] 0.1C charge to 3.4V and let stand for 10 minutes;

[0479] 0.2C charge to 3.65V, let stand for 10min;

[0480] 0.2C charge to 3.75V, let stand for 10min;

[0481] The transformation is finished.

[0482] In this example, the lithium-ion secondary battery obtained by chemical formation was disassembled, and the content of components in the electrolyte was detected. The acetylene additive (Compound II) was 1.7% by mass in the electrolyte.

[0483] In this example, in the negative electrode sheet obtained after cold pressing, the thickness of the negative electrode active layer on one side is 45 μm, and the total thickness on both sides is 90 μm. The prepared lithium-ion secondary battery is disassembled, and the thickness of the negative electrode active layer measured on the negative electrode sheet is about 51 μm on one side, and the total thickness on both sides is about 102 μm.

[0484] Example 2-4. A lithium-ion secondary battery was prepared by a method substantially the same as that of Example 1, except that: in the step of preparing the negative electrode sheet, the single-side coating surface density of the negative electrode active layer was changed, the compaction density was kept consistent with that of Example 1, and the total thickness of the negative electrode active layer in the lithium-ion secondary battery after cold pressing was changed, and the single-side thickness on both sides was substantially the same. The remaining steps were the same as those of Example 1. Please refer to Table 1.

[0485] In Example 2, the total thickness of the negative electrode active layer in the prepared lithium ion secondary battery is 84 μm;

[0486] In Example 3, the total thickness of the negative electrode active layer in the prepared lithium-ion secondary battery is 92 μm;

[0487] In Example 4, the total thickness of the negative electrode active layer in the prepared lithium ion secondary battery was 119 μm.

[0488] Example 5-6. A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that in the step of preparing the negative electrode sheet, the compaction density was changed to adjust the porosity, and the coating surface density was kept the same as that of Example 1. The remaining operation steps were the same as those of Example 1. The test data of the single-side thickness and total thickness of the negative electrode active layer and the porosity of the negative electrode active layer in the prepared lithium ion secondary battery can be found in Table 1.

[0489] Example 7-8. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that different negative electrode active materials were used in the step of preparing the negative electrode sheet, and the compaction density was adjusted to control the porosity to be basically consistent with Table 1. The remaining steps were the same as in Example 1. v 50. The parameter value of the average primary particle size (D1) of the negative electrode active material can be found in Table 1. The test data of the single-side thickness and total thickness of the negative electrode active layer and the porosity of the negative electrode active layer in the prepared lithium-ion secondary battery can be found in Table 1.

[0490] Examples 9-10. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the initial molar volume concentration of the electrolyte lithium salt lithium hexafluorophosphate was changed, and the remaining steps were the same as those of Example 1. See Table 2.

[0491] In Example 9, the initial molar volume concentration of lithium hexafluorophosphate in the electrolyte is 0.7 mol / L;

[0492] In Example 10, the initial molar volume concentration of lithium hexafluorophosphate in the electrolyte is 1.2 mol / L.

[0493] Example 11-12. A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different and the initial concentration of the acetylene additive (Compound IIa) in the electrolyte was different. The remaining steps were the same as those of Example 1. See Table 2.

[0494] In Example 11, the initial mass proportion of the acetylene additive (Compound IIa) in the electrolyte is 0.1%.

[0495] In Example 12, the initial mass proportion of the acetylene additive (Compound IIa) in the electrolyte is 5%.

[0496] Examples 13-17. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the composition of the prepared electrolyte was different and the composition of the additive in the electrolyte was different. The remaining steps were the same as those of Example 1. See Table 2.

[0497] In Example 13, the additive composition in the electrolyte is 3% of Compound IIa and 0.5% of lithium difluorophosphate, based on the initial mass percentage in the electrolyte.

[0498] In Example 14, the additive composition in the electrolyte is: 3% of Compound IIa and 0.5% of LiDFOB (lithium difluorooxalatoborate), based on the initial mass percentage in the electrolyte.

[0499] In Example 15, the additive composition in the electrolyte is: 3% of Compound IIa and 0.5% of TMSP (tris(trimethylsilyl)phosphate), based on the initial mass percentage in the electrolyte.

[0500] In Example 16, the additive composition in the electrolyte is: 3% of Compound IIa and 0.5% of DTD (vinyl sulfate), based on the initial mass percentage in the electrolyte.

[0501] In Example 17, the additive composition in the electrolyte is: 3% of Compound IIa and 0.5% of VC (vinylene carbonate), based on the initial mass percentage in the electrolyte.

[0502] Example 18 A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition, the electrolyte additive composition and the electrolyte lithium salt composition were different, and the remaining steps were the same as those of Example 1. See Table 2.

[0503] In Example 18, the additive composition in the electrolyte is: 3% of Compound IIa and 0.5% of FEC (fluoroethylene carbonate) based on the initial mass percentage in the electrolyte; the electrolyte lithium salt is 0.3 mol / L LiFSI (lithium bis(fluorosulfonyl)imide) and 0.7 mol / L LiPF6 (lithium hexafluorophosphate) based on the initial molar volume concentration in the electrolyte.

[0504] Example 19 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the type of acetylene additive in the electrolyte was different, and the remaining steps were the same as those of Example 1. See Table 2.

[0505] In Example 19, the acetylene additive compound IIa is replaced by methyl carboxylic acid-2-propynyl ester ( ).

[0506] Comparative Example 1. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the electrolyte composition was different, the acetylene additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 1.

[0507] Comparative Example 2. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 17, except that the electrolyte composition was different, the acetylene additive was omitted from the electrolyte, and the initial concentrations of the other additives and the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 17.

[0508] Comparative Example 3. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 18, except that the electrolyte composition was different, the acetylene additive was omitted from the electrolyte, and the initial concentrations of the other additives and the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 18.

[0509] Comparative Example 4 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 19, except that the prepared electrolyte composition was different, the acetylene additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 19.

[0510] Comparative Example 5-6. A lithium-ion secondary battery was prepared by a method substantially the same as that in Example 1, except that: in the step of preparing the negative electrode sheet, the single-side coating surface density of the negative electrode active layer was changed, the compaction density was kept consistent with that in Example 1, and the total thickness of the negative electrode active layer in the lithium-ion secondary battery after cold pressing and obtained was changed, and the single-side thickness on both sides was substantially the same. The remaining operating steps were the same as those in Example 1. Please refer to Table 1.

[0511] In Comparative Example 5, the total thickness of the negative electrode active layer in the prepared lithium ion secondary battery is about 50 μm;

[0512] In Comparative Example 6, the total thickness of the negative electrode active layer in the prepared lithium ion secondary battery was about 150 μm.

[0513] Comparative Example 7-8 A lithium ion secondary battery was prepared by the same method as in Example 1, except that different negative electrode active materials were used in the step of preparing the negative electrode sheet. v 50. The parameter value of the average primary particle size (D1) of the negative electrode active material can be found in Table 1. The test data of the single-side thickness and total thickness of the negative electrode active layer and the porosity of the negative electrode active layer in the prepared lithium-ion secondary battery can be found in Table 1.

[0514] 2. Test and analysis methods

[0515] 1. Battery performance test

[0516] 1. Single-side thickness of the negative electrode active layer

[0517] Measured using a micrometer.

[0518] The test was obtained by the following method: disassemble the battery cell, take out the negative electrode, and use a micrometer to measure the thickness D of the electrode. A .

[0519] Take another negative electrode sheet, wipe off the negative electrode active layer on the surface of the side to be tested, and remove the remaining empty current collector foil. Test the thickness D 10 , then the thickness of the negative electrode active layer on the negative electrode current collector is D A -D 10 .

[0520] 2. Porosity of the negative electrode active layer

[0521] (1) Pretreatment: Use 1 / 2 sample tube to take appropriate amount of sample, heat and vacuum degas for 2h, weigh the total weight after cooling to room temperature, and subtract the mass of the sample tube to get the sample mass. (2) Test: Put the sample tube into the workstation, cover it with a filter plug, and measure the adsorption amount of gas on the solid surface under different adsorption pressures at a constant low temperature. Based on the BET multilayer adsorption theory and its formula, the monolayer adsorption amount of the sample is obtained, and the specific surface area per unit mass of the solid sample is calculated. (3) Adsorption gas: nitrogen, adsorption pressure point: 0-0.01, and test the free space by yourself, test atmosphere: high-purity liquid nitrogen atmosphere.

[0522] The apparent density, true density and porosity of iron ore were tested using the AccuPyc II 1340 fully automatic true density tester from Micromeritics, USA, with reference to the national standard GB / T 24586-2009.

[0523] Test method: 30 small discs with a diameter of 14 mm were cut from the negative electrode sheet. Based on the principle of gas adsorption, inert gas helium was used as the medium to test the true volume of 30 small discs with a diameter of 14 mm. Then, the relationship between the apparent volume and the true volume of the negative electrode sheet was calculated based on the area, thickness and number of the small discs, and the porosity of the negative electrode active layer was calculated.

[0524] (III) Battery performance test

[0525] 1. Battery DCR test

[0526] Initial DC internal resistance (DCR0)

[0527] At 25°C, the battery to be tested is charged to 3.65V at 1C constant current, and then charged to 0.05C at constant voltage; the battery is discharged at 0.5C constant current for 1 hour, and the battery is adjusted to 50% SOC. The battery voltage at this time is recorded as U1; the battery is discharged at 4C constant current for 30 seconds, and the sampling point is taken at 0.1 seconds. The voltage at the end of discharge is recorded as U2. The discharge DCR of the battery at 50% SOC represents the initial DCR of the battery. The initial DCR of the battery = (U1-U2) / I, where I is the current value corresponding to 4C.

[0528] The test results can be found in “Battery DCR0” in Table 3.

[0529] 2. Normal temperature cycle performance

[0530] Test procedure: 25℃, 1C / 1C cycle, voltage range 2.5V~3.65V, capacity retention after 600 cycles.

[0531] Detailed steps: At 25°C, charge the battery to be tested at 1C constant current to 3.65V, then charge at 3.65V constant voltage to a cut-off current of 0.05C, leave for 10 minutes, then discharge at 1C constant current to 2.5V, leave for 5 minutes. This is a charge and discharge cycle. Record the discharge capacity at this time as C0. Repeat this charge and discharge cycle process for the same battery, and record the discharge capacity C of the 1st, 2nd, ... nth cycles. n , where the number of cycles is at least 600.

[0532] Record the battery's cycle capacity retention rate when the cycle is 600 times P600 = C 600 / C0×100%.

[0533] The test results can be found in the "Capacity retention rate after 600 cycles at room temperature" in Table 3. The higher the test value, the better the room temperature cycle life.

[0534] 3. High temperature cycle performance (65°C)

[0535] Test procedure: 65℃, 1C / 1C cycle, voltage range is 2.5V~3.65V, and capacity retention rate is measured after 600 cycles.

[0536] Detailed steps: At 65°C, charge the battery to be tested at 1C constant current to 3.65V, then charge at 3.65V constant voltage to a cut-off current of 0.05C, leave for 10 minutes, then discharge at 1C constant current to 2.5V, leave for 5 minutes. This is a charge and discharge cycle. Record the discharge capacity at this time as C0. Repeat this charge and discharge cycle process for the same battery, and record the discharge capacity C of the first, second, and nth cycles. n , where the number of cycles is at least 600.

[0537] Record the battery's cycle capacity retention rate when the cycle is 600 times P600 = C 600 / C0×100%.

[0538] The test results can be found in the "Capacity retention rate after 600 cycles at 65°C" in Table 3. The higher the test value, the better the high-temperature cycle life.

[0539] 3. Test Analysis Results

[0540] Table 1.

[0541]

[0542] Table 2.

[0543]

[0544] Table 3.

[0545]

[0546] The ionic conductivity of the electrolytes of Examples 1-19 at 25° C. is greater than or equal to 9 mS / cm, and is within the range of 9 mS / cm to 20 mS / cm.

[0547] In Examples 1-19, the tortuosity of the negative electrode plates is in the range of 4 to 6, and the tortuosity of Examples 1, 7, and 8 are 5, 1.2, and 5.7, respectively.

[0548] In Examples 1-19, the active specific surface area of ​​the negative electrode active material is 2 m 2 / g~6m 2 / g, the active specific surface areas of Examples 1, 7, and 8 are 4m 2 / g, 5.8m 2 / g and 2.2m 2 / g.

[0549] In Examples 1 to 19, the Dv1 of the negative electrode active materials all satisfied a value greater than or equal to 1 μm.

[0550] In Examples 1-19, the average primary particle size (D1) of the negative electrode active material is in the range of 0.1 μm to 2 μm, and in Example 1 it is in the range of 0.1 μm to 1 μm.

[0551] In the lithium-ion secondary batteries prepared by chemical formation, the battery cells were disassembled to test the electrolyte components: the mass proportions of acetylene additives in the electrolytes of Examples 1-19 were all in the range of 0.01% to 3.2%. After chemical formation, the mass proportion of acetylene additives in the electrolyte in Example 1 was about 1.7% (initial concentration before formation was 3%), the mass proportion of acetylene additives in the electrolyte in Example 11 was about 0.02% (initial concentration before formation was 0.1%), and the mass proportion of acetylene additives in the electrolyte in Example 12 was about 3% (initial concentration before formation was 5%). The mass percentages of various second additives in the electrolytes of Examples 13-18 were reduced to varying degrees and all still had residues.

[0552] The lithium-ion secondary batteries prepared in Examples 1-19 all have good high-temperature performance and significantly improved room-temperature performance.

[0553] In Comparative Examples 1-4, the acetylene additive in the electrolyte was omitted, and both the high temperature performance and the room temperature performance were significantly deteriorated.

[0554] In Comparative Example 5-6, the thickness of the negative electrode active layer was changed, and both the high temperature performance and the room temperature performance were significantly deteriorated.

[0555] Comparative Example 7-8: Changing the D of the negative electrode active material v 50, both the high temperature performance and the room temperature performance deteriorated significantly, the capacity retention rate after 600 cycles at room temperature was less than 85%, and the capacity retention rate after 600 cycles at high temperature of 65℃ was less than 70%.

[0556] The description of each embodiment and example above tends to emphasize the differences between each embodiment and example, and the same or similar parts can be referenced to each other. For the sake of brevity, this article will not repeat them. The technical features of the above-described embodiments and examples can be combined arbitrarily. For the sake of brevity, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0557] It should be noted that the present application is not limited to the above-mentioned embodiments and examples. The above-mentioned embodiments and examples are only examples. Within the scope of the technical solution of the present application, the embodiments and examples that have the same structure as the technical idea and play the same effect are all included in the technical scope of the present application. The above-described embodiments and examples only express several embodiments and examples of the present application, and the description is relatively detailed, but it cannot be understood as a limitation on the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, various modifications that can be thought of by a person skilled in the art to the embodiments or examples, and other methods of combining some of the constituent elements in the embodiments or examples are also included in the scope of the present application.

Claims

1. A lithium-ion secondary battery cell, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is arranged between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises a negative electrode active material; the negative electrode active material comprises a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%; The electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the additive comprises an acetylene additive, and the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; wherein the first acetylene compound is composed of a carbon-carbon triple bond, a C 1-3 The second alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-O-R2, R2 is C 1-3 Alkyl; the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%; The thickness of the negative electrode active layer on one side of the negative electrode current collector is less than or equal to 60 μm, and the D v 50 is 3μm~15μm.

2. The lithium-ion secondary battery cell according to claim 1, characterized in that: The thickness of the negative electrode active layer on one side of the negative electrode current collector is 40 μm to 55 μm.

3. The lithium-ion secondary battery cell according to claim 1, characterized in that: The thickness of the negative electrode active layer on one side of the negative electrode current collector is 45 μm to 55 μm.

4. The lithium-ion secondary battery cell according to claim 1, characterized in that: The negative electrode active material D v 50 is 3.5μm~15μm.

5. The lithium-ion secondary battery cell according to claim 1, characterized in that: The negative electrode active material comprises a coated negative electrode material, wherein the coated negative electrode material comprises a negative electrode active body and a carbon coating layer located at least in a portion of the negative electrode active body.

6. The lithium-ion secondary battery cell according to claim 5, characterized in that: The negative electrode active material D v 50 is 5μm~14μm.

7. The lithium-ion secondary battery cell according to claim 5, characterized in that: The negative electrode plate meets one or more of the following characteristics: (a1) The mass proportion of the coated negative electrode material in the negative electrode active material is 80% to 100%; (a2) The coated negative electrode material includes coated graphite, and the negative electrode active body in the coated graphite includes a graphite body.

8. The lithium-ion secondary battery cell according to claim 7, characterized in that: The mass proportion of the coated graphite in the negative electrode active material is 80% to 100%.

9. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The porosity of the negative electrode active layer is 14% to 26%.

10. The lithium-ion secondary battery cell according to claim 9, characterized in that: The porosity of the negative electrode active layer is 18% to 22%.

11. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The additive further includes an additive B, and the additive B is one or more of a lithium salt additive and a phosphate ester additive, and the mass ratio of the additive B to the acetylene additive is 0.1-100.

12. The lithium-ion secondary battery cell according to claim 11, characterized in that: The electrolyte satisfies one or more of the following characteristics: (b1) the mass ratio of the additive B to the acetylene additive is 0.3-50; (b2) the lithium salt additive includes one or more of oxalate lithium salt, lithium tetrafluoroborate, lithium difluorophosphate, fluorosulfonic acid lithium salt and lithium perchlorate; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate and lithium bisoxalatoborate; the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethanesulfonate; (b3) the phosphate additive includes one or more of silicon-based phosphate additives and alkylphosphonate additives; the silicon-based phosphate additive includes one or more of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)phosphite; (b4) the additive includes a lithium salt additive, and the mass proportion of the lithium salt additive in the electrolyte is greater than 0 and less than or equal to 3%; (b5) The additive includes a phosphate additive, and the mass proportion of the phosphate additive in the electrolyte is greater than 0 and less than or equal to 1%.

13. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The negative electrode plate meets one or more of the following characteristics: (c1) the negative electrode active material comprises a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is less than or equal to 3%; (c2) the negative electrode active material comprises a silicon-based material, the silicon-based material comprises a silicon-carbon composite material, the silicon-carbon composite material comprises a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%; (c3) The mass proportion of the graphite-based material in the negative electrode active material is 80% to 100%.

14. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The positive electrode plate includes a positive electrode collector and a positive electrode active layer located on at least one side of the positive electrode collector, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide positive electrode material; the thickness of the positive electrode active layer on a single side of the positive electrode collector is less than or equal to 50 μm.

15. The lithium-ion secondary battery cell according to claim 14, characterized in that: The positive electrode active material comprises a lithium nickel-based oxide positive electrode material, wherein the lithium nickel-based oxide positive electrode material comprises a lithium element, a non-lithium metal element and an oxygen element; wherein the non-lithium metal element comprises a nickel element; in the lithium nickel-based oxide positive electrode material, the ratio of the atomic molar ratio of the nickel element to the sum of the atomic molar ratios of the non-lithium metal elements is recorded as R Ni ; R Ni ≥0.8, the thickness of the positive electrode active layer on one side of the positive electrode current collector is 40 μm-50 μm.

16. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The mass proportion of the acetylene additive in the electrolyte is 0.001% to 3.2%.

17. The lithium-ion secondary battery cell according to claim 16, characterized in that: The mass proportion of the acetylene additive in the electrolyte is 0.01% to 1.8%.

18. The lithium-ion secondary battery cell according to claim 16, characterized in that: The lithium-ion secondary battery cell meets one or more of the following characteristics: (d1) The positive electrode sheet comprises a positive electrode active layer, the positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium transition metal oxide positive electrode material; (d2) The negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is less than or equal to 3%; and the acetylene additive includes the first acetylene compound.

19. The lithium-ion secondary battery cell according to any one of claims 1 to 8, characterized in that: The electrolyte satisfies one or more of the following characteristics: (e1) the molecular weight of the acetylene additive is less than or equal to 500 Da; (e2) The carbon-carbon triple bond in the acetylene additive is CH≡C-; (e3) the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 80% to 100%; (e4) The mass proportion of the first acetylenic compound in the acetylenic additive is 80% to 100%.

20. The lithium-ion secondary battery cell according to claim 19, characterized in that: The electrolyte satisfies one or more of the following characteristics: (f1) the molecular weight of the acetylene additive is less than or equal to 300 Da; (f2) The Lewis base nitrogen heterocycle is a substituted or unsubstituted imidazole group, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 an alkyl group, a cyano group or a fluorine atom; (f3) the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 90% to 100%; (f4) The mass proportion of the first acetylenic compound in the acetylenic additive is 90% to 100%.

21. The lithium-ion secondary battery cell according to claim 19, characterized in that: The acetylene additive includes one or more of compound II and compound III; The structure of the compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3; The structure of the compound III is Among them, L 21 C 1-3 Alkylene, R2 is C 1-3 alkyl.

22. A method for preparing a lithium-ion secondary battery monomer, characterized in that: The steps include: An electrode assembly including a positive electrode sheet and a negative electrode sheet is placed in a battery housing; wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material, wherein the negative electrode active material includes a graphite-based material, wherein the mass proportion of the graphite-based material in the negative electrode active material is 60% to 100%; wherein the thickness of the negative electrode active layer on a single side of the negative electrode current collector is less than or equal to 55 μm, and the D of the negative electrode active material is less than or equal to 100%. v 50 is 3μm~15μm; The electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to allow the electrolyte to soak the positive electrode sheet and the negative electrode sheet, and the electrolyte is formed; wherein the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the additive comprises an acetylene additive, and the acetylene additive is a compound containing a carbon-carbon triple bond; the acetylene additive comprises one or more of a first acetylene compound and a second acetylene compound; wherein the first acetylene compound is composed of a carbon-carbon triple bond, a C 1-3 The second alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-O-R2, R2 is C 1-3 Alkyl; the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the acetylene additive is 75% to 100%.

23. The method for preparing a lithium-ion secondary battery monomer according to claim 22, characterized in that: A lithium-ion secondary battery monomer as claimed in any one of claims 2 to 21 is prepared.

24. A battery device, characterized in that: One or more of the lithium-ion secondary battery monomers described in any one of claims 1 to 21 and the lithium-ion secondary battery monomers prepared by the method for preparing the lithium-ion secondary battery monomer described in claim 22; The battery device comprises one or more lithium-ion secondary battery cells.

25. An electrical device, characterized in that: The invention comprises at least one of the lithium ion secondary battery cell according to any one of claims 1 to 21, the lithium ion secondary battery cell prepared by the method for preparing the lithium ion secondary battery cell according to claim 22, and the battery device according to claim 24.

Citation Information

Patent Citations

  • Non-aqueous electrolyte for lithium secondary battery and lithium secondary battery comprising same

    CN113711415A

  • Electrolyte and electrochemical device comprising same

    CN114245947A

  • Battery cell, battery device, and electric device

    CN119153758A

  • Lithium ion secondary battery, cell, and electric device

    CN119340485A

  • Negative electrode plate, and electrochemical device and electronic device comprising negative electrode plate

    WO2024050813A1